Steel sheet, member, and method for producing same

A steel plate with controlled microstructure and composition, combined with specific processing, addresses the formability and fracture resistance challenges of high-strength steel plates, enhancing impact energy absorption in automotive components.

CN119173645APending Publication Date: 2024-12-20JFE STEEL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038649.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-02-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Current high-strength steel plates with TS greater than 590 MPa used in automobile impact energy absorbing components face challenges in maintaining high yield stress and yield ratio while ensuring excellent stamping formability, hole expandability, bendability, and fracture resistance, leading to reduced impact energy absorption during collisions.

Method used

A steel plate composition with controlled microstructure ratios of ferrite, tempered martensite, retained austenite, and bainite, along with specific element contents, combined with controlled cooling and annealing processes, to achieve tensile strength of 780 MPa or more, high yield stress and yield ratio, and improved formability and fracture resistance.

Benefits of technology

The steel plate achieves enhanced stamping formability, hole expandability, bendability, and fracture resistance, allowing for effective impact energy absorption in automotive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173645A_ABST
    Figure CN119173645A_ABST
Patent Text Reader

Abstract

The TS of the steel sheet is 780 MPa or more, and the steel sheet has high YS and YR, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance characteristics (bending fracture characteristics and axial crushing characteristics) at the time of collision. The base steel sheet has a prescribed component composition, and ferrite, fresh martensite, retained austenite, bainite, tempered bainite, and tempered martensite in the steel structure at a position of 1 / 4 of the sheet thickness of the base steel sheet are set to prescribed ranges. The value obtained by dividing the sum of the area ratios of isolated island-like fresh martensite and isolated island-like retained austenite in the ferrite grains by the sum of the area ratio of fresh martensite and the area ratio of retained austenite is 0.65 or more; the average crystal grain size of isolated island-like fresh martensite and isolated island-like retained austenite in the ferrite grains is 2.0 [mu] m or less, and the amount of diffusible hydrogen contained in the base steel sheet is 0.50 ppm by mass or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel plate, a component using the steel plate as a raw material, and a method for producing the same. Background Art

[0002] In order to improve fuel efficiency and thus reduce CO2 emissions and improve collision safety by thinning and lightening the steel plates used in automobile bodies, the high strength of automobile steel plates is being promoted. In addition, new laws and regulations have been introduced one after another. Therefore, for the purpose of increasing the strength of the vehicle body, high-strength steel plates, especially high-strength steel plates with a tensile strength (hereinafter also referred to as TS) of 780MPa or more, are used in the main structural members and reinforcing members (hereinafter also referred to as the skeleton structural members of the automobile, etc.) assembled on the frame of the automobile cab. In addition, high-strength steel plates used for the skeleton structural members of automobiles are required to have high member strength during stamping. Regarding the improvement of component strength, for example, it is effective to increase the yield stress (hereinafter also referred to as YS) of the steel plate divided by TS, that is, the yield ratio (hereinafter also referred to as YR). As a result, the impact absorption energy (hereinafter also referred to as impact absorption energy) during automobile collision increases. In addition, in the skeleton structural members of automobiles, such as collision boxes, there are bending parts. Therefore, for such parts, from the perspective of stamping formability, it is preferred to apply steel plates with high bendability. In addition, from the viewpoint of the rust prevention performance of the vehicle body, the steel sheets used as the raw materials of the automobile parts are often galvanized. Therefore, it is desired to develop a hot-dip galvanized steel sheet having not only high strength but also excellent press formability and impact resistance.

[0003] Regarding such steel sheets as raw materials for automobile components, for example, Patent Document 1 discloses a high-strength steel sheet having excellent stretch flange formability and collision resistance, characterized in that it contains, in mass %, 0.04 to 0.22% C, 1.0% or less Si, 3.0% or less Mn, 0.05% or less P, 0.01% or less S, 0.01 to 0.1% Al and 0.001 to 0.005% N, with the remainder being Fe and inevitable impurities, and is composed of a ferrite phase as a main phase and a martensite phase as a secondary phase, and the maximum grain size of the martensite phase is 2 μm or less, and its area ratio is 5% or more.

[0004] In addition, Patent Document 2 discloses a high-strength hot-dip galvanized steel sheet with excellent coating adhesion and formability, wherein the cold-rolled steel sheet is pre-plated with 0.2 g / m 2 Above and 2.0g / m 2A hot-dip galvanized steel sheet having a hot-dip galvanized layer on the surface of a cold-rolled steel sheet obtained by reducing Ni to less than 7%, characterized in that the steel sheet has a hot-dip galvanized layer on the surface containing less than 7% Fe, and the balance consisting of Zn, Al and inevitable impurities, wherein the tensile strength is TS (MPa), the total elongation is EL (%), and the hole expansion ratio is λ (%), TS×EL is 18000 MPa·% or more, TS×λ is 35000 MPa·% or more, and the steel sheet has a tensile strength of 980 MPa or more, and the steel sheet contains, by mass%, C: 0.05% or more and 0.4% or less, Si: 0.01% or more and 3.0% or less, Mn: 0.1% or more and 3.0% or less, P: 0.04% or less, S: 0.05% or less, N: 0.01% or less, Al: 0.01% or more and 2.0% or less, Si+Al>0.5%, the balance being Fe and inevitable impurities, the microstructure containing 40% or more ferrite as a main phase by volume fraction, 8% or more retained austenite, two or more of martensite [3] among the three martensites [1][2][3] specified below, 1% or more bainite and 0-10% pearlite, wherein the three martensites [1][2][3] are respectively represented by volume fraction as martensite [1]: 0% or more and 50% or less, martensite [2]: 0% or more and less than 20%, martensite [3]: 1% or more and less than 30% (martensite [1]: C concentration (CM1) is less than 0.8%, and hardness Hv1 is Hv1 / (-982.1×CM1 2 +1676×CM1+189)≤0.60, martensite[2]: C concentration (CM2) is above 0.8%, hardness Hv2 is Hv2 / (-982.1×CM2 2 +1676×CM2+189)≤0.60, martensite[3]: C concentration (CM3) is above 0.8%, hardness Hv3 is Hv3 / (-982.1×CM3 2 +1676×CM3+189)≥0.80.

[0005] In addition, Patent Document 3 discloses a high-strength hot-dip galvanized steel sheet having, by mass%, C: 0.15% to 0.25%, Si: 0.50% to 2.5%, Mn: 2.3% to 4.0%, P: 0.100% to 0.100%, S: 0.02% to 0.02%, Al: 0.01% to 2.5%, the remainder being Fe and unavoidable impurities, and having tempered martensite by area ratio. phase: 30% or more and 73% or less, ferrite phase: 25% or more and 68% or less, retained austenite phase: 2% or more and 20% or less, other phases: 10% or less (including 0%), and having a martensite phase: 3% or less (including 0%), a bainitic ferrite phase: less than 5% (including 0%) as the other phases, the average grain size of the tempered martensite phase is 8 μm or less, and the C amount in the retained austenite phase is less than 0.7 mass % of the steel sheet structure.

[0006] In addition, Patent Document 4 discloses an alloyed hot-dip galvanized steel sheet having an alloyed hot-dip galvanized layer on the surface of the steel sheet, characterized in that the steel sheet has, in terms of mass%, C: 0.03% to 0.35%, Si: 0.005% to 2.0%, Mn: 1.0% to 4.0%, P: 0.0004% to 0.1%, S: 0.02%, sol.Al: 0.0002% to 2.0%, N: 0.01%, the remainder being Fe and impurities, and having a chemical composition at a depth of 50 μm from the surface of the steel sheet and at The alloyed hot-dip galvanized steel sheet has a mechanical property of a tensile strength (TS) of 780 MPa or more.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 3887235

[0010] Patent Document 2: Japanese Patent No. 5953693

[0011] Patent Document 3: Japanese Patent No. 6052472

[0012] Patent Document 4: Japanese Patent No. 5699764 Summary of the invention

[0013] Problems to be solved by the invention

[0014] However, in the skeleton components of automobiles represented by the center pillar, the use of steel plates with a tensile strength TS (hereinafter sometimes abbreviated as TS) greater than 590 MPa is being promoted, but the current situation is that the impact energy absorbing components of automobiles represented by the front longitudinal beam and the rear longitudinal beam still use steel plates with a TS of 590 MPa level.

[0015] That is, in order to increase the absorbed energy during a collision (hereinafter also referred to as impact absorbed energy), it is effective to increase the yield stress YS (hereinafter sometimes abbreviated as YS) and the yield ratio YR (hereinafter sometimes abbreviated as YR). However, when the YS and YR of a steel plate are increased, generally the stamping formability, especially the ductility, hole expansion, and bendability, etc., will be reduced. Therefore, when it is assumed that such a steel plate with increased TS and YS is applied to the impact energy absorbing component of the above-mentioned automobile, not only will stamping become difficult, but the component will also break in the axial crushing test of the simulated collision test. In other words, the actual impact absorbed energy will not be as high as expected based on the value of YS. Therefore, the current situation is that the above-mentioned impact energy absorbing component remains at the level of steel plates with a TS of 590MPa.

[0016] In fact, the steel plates disclosed in Patent Documents 1 to 4 can also be said to be steel plates having a TS of 780 MPa or above and having high YS and YR, excellent stamping formability (ductility, hole expandability and bendability) and fracture resistance during collision (bending fracture characteristics and axial crushing characteristics).

[0017] The present invention has been developed in view of the above-mentioned situation, and its purpose is to provide a steel plate and a method for manufacturing the same having a tensile strength TS of more than 780 MPa, a high yield stress YS and a high yield ratio YR, excellent stamping formability (ductility, hole expandability and bendability) and fracture resistance during collision (bending fracture characteristics and axial crushing characteristics).

[0018] Another object of the present invention is to provide a member using the above-mentioned steel plate as a raw material and a method for producing the same.

[0019] It should be noted that the steel sheet mentioned here also includes galvanized steel sheet, and the galvanized steel sheet refers to hot-dip galvanized steel sheet (hereinafter also referred to as GI) or alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA).

[0020] In addition, here, the tensile strength TS can be measured by a tensile test in accordance with JIS Z 2241 (2011).

[0021] In addition, the high yield stress YS and yield ratio YR mean that YS measured in a tensile test in accordance with JIS Z 2241 (2011) satisfies the following formula (A) or (B) based on TS measured in the tensile test.

[0022] (A) When 780MPa≤TS<980MPa, 500MPa≤YS and 0.64≤YR

[0023] (B) When 980MPa≤TS, 600MPa≤YS and 0.61≤YR

[0024] In addition, excellent ductility means that the total elongation (E1) measured in a tensile test in accordance with JIS Z 2241 (2011) satisfies the following formula (A) or (B) based on TS measured by the tensile test.

[0025] (A) When 780MPa≤TS<980MPa, 19.0%≤El

[0026] (B) When 980MPa≤TS, 15.0%≤El

[0027] In addition, excellent hole expandability means that the limiting hole expansion ratio (λ) measured in the hole expansion test in accordance with JIS Z 2256 (2020) is 30% or more.

[0028] Moreover, the term "excellent bendability" means that R (limit bending radius) / t (sheet thickness) measured in a V-bend test in accordance with JIS Z 2248 (2014) satisfies the following formula (A) or (B) based on TS.

[0029] (A) In the case of 780MPa≤TS<980MPa, it means 2.0≥R / t

[0030] (B) In the case of 980 MPa≤TS, it means 2.5≥R / t.

[0031] Furthermore, the term "excellent axial crush characteristics" means that the limiting spacer thickness (ST) in the U-bend + contact bend test satisfies the following formula (A) or (B) based on TS.

[0032] (A) When 780MPa≤TS<980MPa, 2.5mm≥ST

[0033] (B) When 980MPa≤TS, 4.0mm≥ST

[0034] Furthermore, the excellent axial crush characteristics mean that the stroke (SFmax) at the maximum load measured in the V bending + orthogonal VDA bending test satisfies the following formula (A) or (B) according to TS.

[0035] (A) When 780MPa≤TS<980MPa, 28.0mm≤SFmax

[0036] (B) When 980MPa≤TS, 26.5mm≤SFmax

[0037] In addition, excellent axial crushing characteristics refer to the fracture (appearance crack) after the axial crushing test. Figure 4 (b) The lower two curved ridges have R = 5.0 mm and 200 mm (refer to Figure 4 The area Cx) in (a) and (b) is one or less.

[0038] In addition, excellent bending fracture characteristics mean that the limit spacer thickness (ST) in the above-mentioned U-bending + close-fitting bending test satisfies the above-mentioned formula (A) or (B) according to TS, and the stroke (SFmax) at the maximum load measured in the V-bending + orthogonal VDA bending test satisfies the above-mentioned formula (A) or (B) according to TS.

[0039] The above-mentioned El (ductility), λ (stretch flangeability) and R / t (bendability) are characteristics indicating the ease of forming of the steel sheet during press forming (the degree of freedom of forming for press forming without breaking). On the other hand, the U-bend + close-fitting bend test is a test simulating the deformation and fracture behavior of the longitudinal wall portion in a collision test, and the limit spacer thickness (ST) measured in the U-bend + close-fitting bend test is an indicator indicating the ease of fracture of the steel sheet and components of the automobile body during collision (impact resistance characteristics for absorbing impact energy without breaking).

[0040] The V-bend + orthogonal VDA bend test is a test that simulates the deformation and fracture behavior of the bending ridge in a collision test. The stroke (SFmax) at the maximum load measured in the V-bend + orthogonal VDA bend test is an indicator of the easiness of rupture of the energy absorbing member.

[0041] Methods used to solve problems

[0042] The present inventors have conducted intensive studies to solve the above-mentioned problems and have obtained the following findings.

[0043] (1) By controlling the area ratio of tempered martensite to 10.0% or more with a predetermined composition, reducing the island-shaped hard second phase (martensite + retained austenite) in contact with the ferrite grain boundary, and increasing the ratio of isolated fine island-shaped hard second phase (martensite + retained austenite) in the ferrite grains, a TS of 780 MPa or more can be ensured.

[0044] (2) By controlling the area ratio of tempered martensite to 10.0% or more with a predetermined composition and reducing the island-shaped hard second phase (martensite + retained austenite) in contact with the ferrite grain boundary, high YS and YR can be ensured.

[0045] (3) By controlling the area ratio of ferrite to 20.0% or more with a predetermined composition, ductility (related to stretch formability which is one mode of press formability) can be improved.

[0046] (4) By controlling the area ratio of fresh martensite to less than 15.0%, the area ratio of retained austenite to less than 3.0%, the area ratio of tempered martensite to more than 10.0% with specified composition, and increasing the ratio of isolated fine island-shaped hard second phase (martensite + retained austenite) in ferrite grains, the hole expandability related to stretch flangeability, which is a mode of stamping formability, can be improved.

[0047] (5) By controlling the area ratio of fresh martensite to less than 15.0%, the area ratio of retained austenite to less than 3.0%, the area ratio of tempered martensite to more than 10.0% with specified composition, and increasing the ratio of isolated fine island-shaped hard second phase (martensite + retained austenite) in ferrite grains, the bendability, which is a mode of stamping formability, can be improved.

[0048] (6) By controlling the area ratio of retained austenite to 3.0% or less with Si: 0.75% by mass or less and the prescribed composition, the formation of hard fresh martensite generated by the process-induced phase transformation of retained austenite generated during primary processing such as blanking and press forming can be controlled, and the formation of voids and the extension of cracks can be suppressed in subsequent tests. In addition, by controlling the area ratio of tempered martensite to 10.0% or more and increasing the ratio of isolated fine island-shaped hard second phases (martensite + retained austenite) in ferrite grains, the limiting spacer thickness (ST) measured in the U-bending + close bending test simulating the deformation and fracture behavior of the longitudinal wall portion in the collision test and the stroke (SFmax) at the maximum load measured in the V-bending + orthogonal VDA bending test simulating the deformation and fracture behavior of the bending ridge portion in the collision test, which are indicators of the impact resistance of the steel sheet and components of the automobile body during collision, can be improved.

[0049] The present invention has been completed based on the above findings. That is, the gist of the present invention is as follows.

[0050] [1] A steel plate having a base steel plate, wherein:

[0051] The base steel plate has a composition containing, in mass%, C: 0.030% to 0.250% inclusive, Si: 0.01% to 0.75% inclusive, Mn: 2.00% to less than 3.50%, P: 0.001% to 0.100% inclusive, S: 0.0200% to inclusive, Al: 0.010% to 2.000% inclusive, N: 0.0100% to inclusive, and the balance being Fe and inevitable impurities, and

[0052] A steel structure having, in terms of the structure at a position 1 / 4 of the plate thickness of the base steel plate, an area ratio of ferrite of 20.0% or more and 80.0% or less, an area ratio of fresh martensite of 15.0% or less, an area ratio of retained austenite of 3.0% or less, a value obtained by dividing the total area ratio of island-shaped fresh martensite and island-shaped retained austenite in ferrite grains by the total area ratio of fresh martensite and retained austenite in the entire steel plate of 0.65 or more, an area ratio of bainite and tempered bainite of 10.0% or less, an area ratio of tempered martensite of 10.0% or more and 70.0% or less, and an average grain size of island-shaped fresh martensite and island-shaped retained austenite in ferrite grains of 2.0 μm or less,

[0053] The amount of diffusible hydrogen contained in the base steel plate is 0.50 mass ppm or less,

[0054] The tensile strength of the steel plate is 780 MPa or more.

[0055] [2] The steel sheet according to [1], wherein the component composition further contains, in mass %, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, and Mg: 0.0200% or less. , Zn: less than 0.0200%, Co: less than 0.0200%, Zr: less than 0.1000%, Ca: less than 0.0200%, Se: less than 0.0200%, Te: less than 0.0200%, Ge: less than 0.0200%, As: less than 0.0500%, Sr: less than 0.0200%, Cs: less than 0.0200%, Hf: less than 0.0200%, Pb: less than 0.0200%, Bi: less than 0.0200% and REM: less than 0.0200%.

[0056] [3] The steel sheet according to [1] or [2], wherein a zinc plating layer is provided as an outermost layer on one or both surfaces of the steel sheet.

[0057] [4] The steel plate according to any one of [1] to [3] above, wherein

[0058] When the base steel plate has a surface layer of a region of 200 μm or less in the plate thickness direction from the surface of the base steel plate,

[0059] The surface layer has a surface soft layer having a Vickers hardness of 85% or less relative to the Vickers hardness at a position of 1 / 4 of the plate thickness,

[0060] When the nanohardness is measured at 300 points or more in a 50 μm×50 μm area of ​​the plate surface at each of the 1 / 4 position and the 1 / 2 position of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate,

[0061] The ratio of the number of measurements of the plate surface having a nanohardness of 7.0 GPa or more at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 0.10 or less relative to the total number of measurements at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer,

[0062] Furthermore, the standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 1.8 GPa or less,

[0063] Furthermore, a standard deviation σ of the nanohardness of the plate surface at a position 1 / 2 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 2.2 GPa or less.

[0064] [5] The steel sheet according to any one of [1] to [4] above, wherein the steel sheet has a metal plating layer formed on the base steel sheet on one or both surfaces of the steel sheet.

[0065] [6] A member formed using the steel plate according to any one of [1] to [5] above.

[0066] [7] A method for manufacturing a steel plate, comprising:

[0067] A hot rolling step, wherein the steel slab having the composition described in [1] or [2] is hot rolled at a finishing temperature of 820° C. or higher to obtain a hot rolled steel sheet;

[0068] A heating step, wherein the steel sheet after the hot rolling step is heated within a temperature range of 350° C. to 600° C. at an average heating rate of 7° C. / s or more;

[0069] An annealing step, wherein the annealing is performed under the conditions of an annealing temperature of 750° C. or higher and 900° C. or lower and an annealing time of 20 seconds or longer;

[0070] A first cooling step, wherein cooling is performed after the annealing step under conditions where the average cooling rate from (the annealing temperature - 30°C) to 650°C is set to 7°C / sec or more, and the average cooling rate from 650°C to 500°C is set to 14°C / sec or less;

[0071] The second cooling step comprises applying 2.0 kgf / mm2 to the steel plate in a temperature range of 300°C to 450°C after the first cooling step. 2 The steel sheet is then subjected to a tension of at least 500 mm and at most 1500 mm, and then subjected to at least 5 passes while being brought into contact with a roll having a diameter of at least 500 mm and at most 1500 mm for 1 / 4 of the roll in each pass, and then cooled to a cooling stop temperature of at most 250° C.; and

[0072] a reheating step, wherein after the second cooling step, the steel sheet is reheated to a temperature in the range of not less than the cooling stop temperature and not more than 440° C. and maintained for 20 seconds or more,

[0073] Alternatively, the method further includes performing cold rolling on the steel sheet after the hot rolling step and before the temperature raising step at a reduction ratio of 20% to 80% to obtain a cold-rolled steel sheet.

[0074] [8] The method for manufacturing a steel sheet according to [7] above, further comprising a galvanizing step of galvanizing the steel sheet after the first cooling step and before the second cooling step to form a zinc plating layer on the steel sheet.

[0075] [9] The method for producing a steel sheet according to [7] or [8] above, wherein the annealing in the annealing step is performed in an atmosphere having a dew point of -30°C or higher.

[0076]

[10] The method for manufacturing a steel plate according to any one of [7] to [9] above, comprising a metal plating step of plating metal on one or both surfaces of the steel plate to form a metal plating layer after the hot rolling step and before the annealing step.

[0077]

[11] A method for manufacturing a component, comprising the step of subjecting the steel plate according to any one of [1] to [5] above to at least one of forming and joining to produce the component.

[0078] Effects of the Invention

[0079] According to the present invention, a steel plate can be obtained which has a tensile strength TS of more than 780 MPa and has a high yield stress YS and yield ratio YR, excellent stamping formability (ductility, hole expandability and bendability) and fracture resistance during collision (bending fracture characteristics and axial crushing characteristics).

[0080] In addition, since the components made of the steel sheet of the present invention are high-strength and have excellent press formability and impact resistance, they can be used very advantageously in automotive frame components, impact energy absorbing components, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 This is an example of the SEM image of the present invention (Example No. 13 of the present invention in the Examples).

[0082] Figure 2 (a) is a diagram for explaining the U-bending process (primary bending process) in the U-bending + close-fit bending test of the example. Figure 2 (b) is a diagram for explaining the close bending process (secondary bending process) in the U-bending + close bending test of the example.

[0083] Figure 3 (a) is a diagram for explaining the V-bending process (primary bending process) in the V-bending + orthogonal VDA bending test of the example. Figure 3 (b) is a diagram for explaining the orthogonal VDA bending process (secondary bending process) in the V-bending + orthogonal VDA bending test of the example.

[0084] Figure 4 (a) is a front view of a test member produced for the shaft crushing test of the example, in which a hat-shaped member and a steel plate are spot-welded. Figure 4 (b) Yes Figure 4 (a) is a perspective view of the test component shown. Figure 4 (c) is a schematic diagram for explaining the shaft crushing test of the example. DETAILED DESCRIPTION

[0085] The present invention will be described based on the following embodiments.

[0086] [1.Steel plate]

[0087] The steel plate of the present invention is a steel plate having a base steel plate, wherein the base steel plate has a component composition containing, by mass%, C: 0.030% or more and 0.250% or less, Si: 0.01% or more and 0.75% or less, Mn: 2.00% or more and less than 3.50%, P: 0.001% or more and 0.100% or less, S: 0.0200% or less, Al: 0.010% or more and 2.000% or less, N: 0.0100% or less, and the balance being Fe and inevitable impurities, and has an area ratio of ferrite of 20.0% or more and 80.0% or less, and an area ratio of fresh martensite of 20.0% or more and 80.0% or less in terms of the structure at a position of 1 / 4 of the plate thickness of the base steel plate. The steel structure comprises a steel sheet having an area ratio of 15.0% or less, an area ratio of retained austenite of 3.0% or less, a value obtained by dividing the total area ratio of fresh martensite and retained austenite in the ferrite grains by the total area ratio of fresh martensite and retained austenite in the entire steel plate by 0.65 or more, an area ratio of bainite and tempered bainite of 10.0% or less, an area ratio of tempered martensite of 10.0% or more and 70.0% or less, and an average grain size of fresh martensite and retained austenite in the ferrite grains of 2.0 μm or less, an amount of diffusible hydrogen contained in the base steel sheet of 0.50 mass ppm or less, and a tensile strength of the steel sheet of 780 MPa or more.

[0088] The steel sheet may have a zinc coating as the outermost layer on one or both surfaces of the steel sheet. The steel sheet having the zinc coating may also be a galvanized steel sheet.

[0089] Ingredients

[0090] First, the component composition of the base steel sheet of the steel sheet according to one embodiment of the present invention will be described. It should be noted that the unit in the component composition is "mass %", and hereinafter, "%" is used only unless otherwise specified.

[0091] C: 0.030% or more and 0.250% or less

[0092] C is an element effective for generating appropriate amounts of tempered martensite, bainite, and tempered bainite, etc., and for ensuring TS of 780 MPa or more, high YS, and high YR. Here, when the C content is less than 0.030%, the area ratio of ferrite increases, making it difficult to make TS of 780 MPa or more. In addition, it also leads to a decrease in YS and YR.

[0093] On the other hand, when the C content is greater than 0.250%, the area ratio of fresh martensite increases, TS becomes too high, and El decreases. In addition, the area ratio of fresh martensite increases, the bendability of the V bending test decreases, and the desired R / t (stamping formability) cannot be obtained. Moreover, the area ratio of retained austenite increases, and when the steel plate is subjected to punching in the hole expansion test, when subjected to U bending in the U bending + close bending test, or when subjected to V bending in the V bending + orthogonal VDA test, hard fresh martensite generated by the processing induced phase transformation of retained austenite is generated, and the generation of voids and the expansion of cracks occur in subsequent tests, and the desired λ (stamping formability), ST (fracture resistance during collision) and SFmax (fracture resistance during collision) cannot be obtained. Therefore, the C content is set to more than 0.030% and less than 0.250%. The C content is preferably more than 0.050%. In addition, the C content is preferably less than 0.130%.

[0094] Si: 0.01% or more and 0.75% or less

[0095] Si promotes ferrite transformation during annealing and in the cooling process after annealing. That is, Si is an element that affects the area ratio of ferrite. Here, when the Si content is less than 0.01%, the area ratio of ferrite decreases and ductility decreases.

[0096] On the other hand, when the Si content is greater than 0.75%, the volume fraction of retained austenite increases, and when the steel plate is subjected to punching in the hole expansion test, when subjected to U bending in the U bending + close bending test, or when subjected to V bending in the V bending + orthogonal VDA test, hard fresh martensite generated by the processing induced phase transformation of the retained austenite is generated, and the generation of voids and the expansion of cracks occur in subsequent tests, and the desired λ, ST and SFmax cannot be obtained. Therefore, the Si content is set to 0.01% or more and 0.75% or less. The Si content is preferably 0.10% or more. In addition, the Si content is preferably 0.70% or less.

[0097] Mn: 2.00% or more and less than 3.50%

[0098] Mn is an element that adjusts the area ratio of tempered martensite, bainite, and tempered bainite. Here, when the Mn content is less than 2.00%, the area ratio of ferrite increases, making it difficult to make TS above 780 MPa. In addition, it also leads to a decrease in YS and YR.

[0099] On the other hand, when the Mn content is 3.50% or more, the martensitic transformation start temperature Ms (hereinafter also referred to as Ms point or Ms) decreases, and the martensite generated in the first cooling process decreases. As a result, the fresh martensite generated in the second cooling process increases, and the fresh martensite cannot be fully tempered in the subsequent reheating process, the area ratio of the fresh martensite increases, the bendability of the V bending test decreases, and the desired R / t cannot be obtained. Therefore, the Mn content is set to be 2.00% or more and less than 3.50%. The Mn content is preferably 2.30% or more. In addition, the Mn content is preferably 3.00% or less.

[0100] P: 0.001% or more and 0.100% or less

[0101] P is an element that has a solid solution strengthening effect and improves TS and YS of the steel plate. In order to obtain such an effect, the P content is set to 0.001% or more.

[0102] On the other hand, when the P content is greater than 0.100%, P segregates at the original austenite grain boundary and embrittles the grain boundary. Therefore, during the V-bending test, the generation of voids and the expansion of cracks occur along the original austenite grain boundary, and the desired R / t cannot be obtained. In addition, when the steel plate is subjected to punching in the hole expansion test, when subjected to U bending in the U-bending + close bending test, or when subjected to V bending in the V-bending + orthogonal VDA test, the generation of voids and the expansion of cracks occur along the original austenite grain boundary, and the desired λ, ST and SFmax cannot be obtained. Therefore, the P content is set to be greater than 0.001% and less than 0.100%. The P content is preferably less than 0.030%.

[0103] S: 0.0200% or less

[0104] S exists in the steel in the form of sulfides. In particular, when the S content is greater than 0.0200%, voids are generated and cracks are extended from the sulfides as the starting point during the V-bending test, and the desired R / t cannot be obtained. In addition, when the steel plate is subjected to punching in the hole expansion test, U-bending in the U-bending + close bending test, or V-bending in the V-bending + orthogonal VDA test, voids are generated and cracks are extended from the sulfides as the starting point, and the desired λ, ST, and SFmax cannot be obtained. Therefore, the S content is set to 0.0200% or less. The S content is preferably 0.0080% or less.

[0105] It should be noted that the lower limit of the S content is not particularly limited, but due to limitations in production technology, the S content is preferably set to 0.0001% or more.

[0106] Al: 0.010% or more and 2.000% or less

[0107] Al promotes ferrite transformation during annealing and in the cooling process after annealing. That is, Al is an element that affects the area ratio of ferrite. Here, when the Al content is less than 0.010%, the area ratio of ferrite decreases and ductility decreases.

[0108] On the other hand, when the Al content is greater than 2.000%, the area ratio of ferrite increases excessively, making it difficult to make TS greater than 780 MPa. In addition, it also leads to a decrease in YS and YR. Therefore, the Al content is set to be greater than 0.010% and less than 2.000%. The Al content is preferably greater than 0.015%. In addition, the Al content is preferably less than 1.000%.

[0109] N: 0.0100% or less

[0110] N exists in the steel in the form of nitrides. In particular, when the N content is greater than 0.0100%, during the V-bending test, voids are generated and cracks are expanded starting from the above nitrides, and the desired R / t cannot be obtained. In addition, when the steel plate is subjected to punching in the hole expansion test, when subjected to U bending in the U bending + close bending test, or when subjected to V bending in the V bending + orthogonal VDA test, voids are generated and cracks are expanded starting from the above nitrides, and the desired λ, ST and SFmax cannot be obtained. Therefore, the N content is set to 0.0100% or less. In addition, the N content is preferably 0.0050% or less.

[0111] It should be noted that the lower limit of the N content is not particularly limited, but due to limitations in production technology, the N content is preferably 0.0005% or more.

[0112] The basic component composition of the base steel sheet of the steel sheet according to one embodiment of the present invention has been described above. The base steel sheet of the steel sheet according to one embodiment of the present invention has a component composition containing the above-mentioned basic components, and the balance other than the above-mentioned basic components includes Fe (iron) and inevitable impurities. Here, the base steel sheet of the steel sheet according to one embodiment of the present invention preferably has a component composition containing the above-mentioned basic components, and the balance consists of Fe and inevitable impurities.

[0113] The base steel sheet of the steel sheet according to one embodiment of the present invention may contain at least one of the optional components shown below in addition to the above-mentioned basic components. It should be noted that the effect of the present invention can be obtained as long as the optional components shown below contain less than the upper limit amount shown below, so no lower limit is particularly set. It should be noted that when the optional elements shown below are contained in an amount less than the preferred lower limit value described below, the elements are contained as unavoidable impurities.

[0114] Selected from Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co At least one of: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, and REM: 0.0200% or less

[0115] Nb: 0.200% or less

[0116] Nb forms fine carbides, nitrides or carbonitrides during hot rolling and annealing, thereby improving TS, YS and YR. In order to obtain such effects, the Nb content is preferably set to 0.001% or more. The Nb content is more preferably 0.005% or more.

[0117] On the other hand, when the Nb content is greater than 0.200%, there is a case where a large amount of coarse precipitates and inclusions are generated. In such a case, the coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, the V bending test, the U bending + close bending test, or the V bending + orthogonal VDA bending test, so there is a case where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, when Nb is contained, the Nb content is preferably 0.200% or less. The Nb content is more preferably 0.060% or less.

[0118] Ti: 0.200% or less

[0119] Ti, like Nb, forms fine carbides, nitrides, or carbonitrides during hot rolling and annealing, thereby increasing TS, YS, and YR. In order to obtain such effects, the Ti content is preferably set to 0.001% or more. The Ti content is more preferably 0.005% or more.

[0120] On the other hand, when the Ti content is greater than 0.200%, there is a situation where a large amount of coarse precipitates and inclusions are generated. In such a case, the coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, the V bending test, the U bending + close bending test or the V bending + orthogonal VDA bending test, so there is a situation where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, when Ti is contained, the Ti content is preferably 0.200% or less. The Ti content is more preferably 0.060% or less.

[0121] V: 0.200% or less

[0122] V, like Nb and Ti, forms fine carbides, nitrides or carbonitrides during hot rolling and annealing, thereby improving TS and YS. In order to obtain such an effect, the V content is preferably set to 0.001% or more. The V content is more preferably 0.005% or more. The V content is further preferably 0.010% or more, and further more preferably 0.030% or more.

[0123] On the other hand, when the V content is greater than 0.200%, there is a situation where a large amount of coarse precipitates and inclusions are generated. In such a case, the coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, the V bending test, the U bending + close bending test or the V bending + orthogonal VDA bending test, so there is a situation where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, when V is contained, the V content is preferably 0.200% or less. The V content is more preferably 0.060% or less.

[0124] B: 0.0100% or less

[0125] B is an element that improves hardenability by segregating at austenite grain boundaries. In addition, B is an element that suppresses the generation of ferrite and grain growth during cooling after annealing. In order to obtain such an effect, it is preferred that B content is set to more than 0.0001%. B content is more preferably more than 0.0002%.

[0126] The B content is more preferably 0.0005% or more, and still more preferably 0.0007% or more.

[0127] On the other hand, when the B content is greater than 0.0100%, cracks may occur inside the steel sheet during hot rolling. In addition, during the hole expansion test, V bending test, U bending + close bending test, or V bending + orthogonal VDA bending test, the internal cracks become the starting point of cracking, so there is a case where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, when B is contained, the B content is preferably set to 0.0100% or less. The B content is more preferably 0.0050% or less.

[0128] Cr: 1.000% or less

[0129] Cr is an element that improves hardenability. Therefore, by adding Cr, an appropriate amount of tempered martensite is generated, thereby improving TS, YS and YR. In order to obtain such an effect, the Cr content is preferably set to 0.0005% or more. In addition, the Cr content is more preferably 0.010% or more.

[0130] The Cr content is more preferably 0.030% or more, and still more preferably 0.050% or more.

[0131] On the other hand, when the Cr content exceeds 1.000%, the area ratio of fresh martensite increases, the hole expandability and the bendability in the V bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when Cr is contained, the Cr content is preferably set to 1.000% or less. In addition, the Cr content is more preferably 0.800% or less, and further preferably 0.700% or less.

[0132] Ni: 1.000% or less

[0133] Ni is an element that improves hardenability. Therefore, by adding Ni, tempered martensite is generated in large quantities, thereby improving TS, YS and YR. In order to obtain such an effect, it is preferred that the Ni content is set to more than 0.005%. The Ni content is more preferably more than 0.020%. The Ni content is further preferably more than 0.040%, and further more preferably more than 0.060%.

[0134] On the other hand, when the Ni content exceeds 1.000%, the area ratio of fresh martensite increases, the hole expandability and the bendability of the V bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when Ni is contained, the Ni content is preferably set to 1.000% or less. The Ni content is more preferably 0.800% or less.

[0135] The Ni content is more preferably 0.600% or less, and still more preferably 0.400% or less.

[0136] Mo: 1.000% or less

[0137] Mo is an element that improves hardenability. Therefore, by adding Mo, tempered martensite is generated in large quantities, thereby improving TS, YS and YR. In order to obtain such an effect, the Mo content is preferably set to 0.010% or more. The Mo content is more preferably 0.030% or more.

[0138] On the other hand, when the Mo content exceeds 1.000%, the area ratio of fresh martensite increases, the hole expandability and the bendability of the V bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when Mo is contained, the Mo content is preferably set to 1.000% or less. The Mo content is more preferably 0.500% or less, further preferably 0.450% or less, and further more preferably 0.400% or less. The Mo content is more preferably 0.350% or less, and further more preferably 0.300% or less.

[0139] Sb: 0.200% or less

[0140] Sb is an element effective for suppressing the diffusion of C near the surface of the steel plate during annealing and controlling the formation of a soft layer near the surface of the steel plate. When the soft layer near the surface of the steel plate increases excessively, it is difficult to set TS to 780MPa or more. In addition, there is a possibility of causing a decrease in YS. Therefore, it is preferred to set the Sb content to 0.002% or more. The Sb content is more preferably 0.005% or more.

[0141] On the other hand, when the Sb content exceeds 0.200%, a soft layer may not be formed near the surface of the steel sheet, resulting in a decrease in λ, R / t, ST, and SFmax. Therefore, when Sb is contained, the Sb content is preferably set to 0.200% or less. The Sb content is more preferably 0.020% or less.

[0142] Sn: 0.200% or less

[0143] Sn is an element that is effective for suppressing the diffusion of C near the surface of the steel sheet during annealing and controlling the formation of a soft layer near the surface of the steel sheet, similarly to Sb. When the soft layer near the surface of the steel sheet increases excessively, it is difficult to set TS to more than 780MPa. In addition, there is also the possibility of causing a decrease in YS. Therefore, it is preferred that the Sn content be set to more than 0.002%. The Sn content is more preferably more than 0.005%.

[0144] On the other hand, when the Sn content exceeds 0.200%, a soft layer may not be formed near the surface of the steel sheet, resulting in a decrease in λ, R / t, ST, and SFmax. Therefore, when Sn is contained, the Sn content is preferably set to 0.200% or less. The Sn content is more preferably 0.020% or less.

[0145] Cu: 1.000% or less

[0146] Cu is an element that improves hardenability. Therefore, by adding Cu, tempered martensite is generated in large quantities, thereby improving TS, YS and YR. In order to obtain such an effect, it is preferred that the Cu content is set to more than 0.005%. The Cu content is more preferably more than 0.008%, and further more preferably more than 0.010%. The Cu content is more preferably more than 0.020%.

[0147] On the other hand, when Cu content is greater than 1.000%, there is a situation where the area ratio of fresh martensite is excessively increased. In addition, there is a situation where a large number of coarse precipitates and inclusions are generated. In such a case, the fresh martensite and coarse precipitates and inclusions generated excessively become the starting points of voids and cracks when the hole expansion test, the V bending test, the U bending+closed bending test or the V bending+orthogonal VDA bending test, so there is a situation where desired λ, R / t, ST and SFmax cannot be obtained. Therefore, when containing Cu, Cu content is preferably set to below 1.000%. The content of Cu is more preferably below 0.200%.

[0148] Ta: 0.100% or less

[0149] Ta, like Ti, Nb and V, forms fine carbides, nitrides or carbonitrides during hot rolling and annealing, thereby increasing TS, YS and YR. Moreover, a portion of Ta is dissolved in Nb carbides and Nb carbonitrides to form composite precipitates such as (Nb, Ta) (C, N). Thus, the coarsening of precipitates is suppressed, and precipitation strengthening is stabilized. Thus, TS and YS are further increased. In order to obtain such an effect, it is preferred that the Ta content is set to 0.001% or more. The Ta content is further preferably 0.002% or more, and further preferably 0.004% or more.

[0150] On the other hand, when the Ta content exceeds 0.100%, a large amount of coarse precipitates and inclusions may be generated. In such a case, excessively coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, V bending test, U bending + close bending test, or V bending + orthogonal VDA bending test, so the desired λ, R / t, ST and SFmax may not be obtained. Therefore, when Ta is contained, the Ta content is preferably 0.100% or less.

[0151] The Ta content is more preferably 0.090% or less, and still more preferably 0.080% or less.

[0152] W: 0.500% or less

[0153] W is an element that improves hardenability. Therefore, by adding W, tempered martensite is generated in large quantities, thereby improving TS, YS and YR. In order to obtain such an effect, it is preferred that the W content is set to 0.001% or more. The W content is more preferably 0.030% or more.

[0154] On the other hand, when the W content exceeds 0.500%, the area ratio of fresh martensite increases, the hole expandability and the bendability in the V bend test decrease, and the desired λ and R / t may not be obtained. Therefore, when W is contained, the W content is preferably set to 0.500% or less. The W content is more preferably 0.450% or less, and further preferably 0.400% or less. The W content is further more preferably 0.300% or less.

[0155] Mg: 0.0200% or less

[0156] Mg is an element effective for spheroidizing the shape of inclusions such as sulfides and oxides and improving the hole expandability and bendability of the steel sheet. In order to obtain such effects, the Mg content is preferably set to 0.0001% or more. The Mg content is more preferably 0.0005% or more, and further preferably 0.0010% or more.

[0157] On the other hand, when the Mg content is greater than 0.0200%, there is a situation where a large number of coarse precipitates and inclusions are generated. In such a case, too coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, the V bending test, the U bending + close bending test or the V bending + orthogonal VDA bending test, so there is a situation where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, when containing Mg, the Mg content is preferably set to less than 0.0200%. The Mg content is more preferably less than 0.0180%, and further preferably less than 0.0150%.

[0158] Zn: 0.0200% or less

[0159] Zn is an element effective for spheroidizing the shape of inclusions and improving the hole expandability and bendability of the steel plate. In order to obtain such effects, the Zn content is preferably set to 0.0010% or more. The Zn content is more preferably 0.0020% or more, and further preferably 0.0030% or more.

[0160] On the other hand, when the Zn content is greater than 0.0200%, there is a situation where a large number of coarse precipitates and inclusions are generated. In such a case, too coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, the V bending test, the U bending + close bending test or the V bending + orthogonal VDA bending test, so there is a situation where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, in the case of containing Zn, the Zn content is preferably set to 0.0200% or less. The Zn content is more preferably 0.0180% or less, and further preferably 0.0150% or less.

[0161] Co: 0.0200% or less

[0162] Co is an element effective for spheroidizing the shape of inclusions and improving the hole expandability and bendability of the steel plate, similarly to Zn. In order to obtain such an effect, the Co content is preferably set to 0.0010% or more. The Co content is more preferably 0.0020% or more, and further preferably 0.0030% or more.

[0163] On the other hand, when the Co content is greater than 0.0200%, there is a situation where a large number of coarse precipitates and inclusions are generated. In such a case, too coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, the V bending test, the U bending + close bending test or the V bending + orthogonal VDA bending test, so there is a situation where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, in the case of containing Co, the Co content is preferably set to 0.0200% or less. The Co content is more preferably 0.0180% or less, and further preferably 0.0150% or less.

[0164] Zr: 0.1000% or less

[0165] Zr is an element that is effective for spheroidizing the shape of inclusions and improving the hole expansion and bendability of the steel plate, just like Zn and Co. In order to obtain such an effect, the Zr content is preferably set to 0.0010% or more. On the other hand, when the Zr content is greater than 0.1000%, in such a case, excessively coarse precipitates and inclusions become the starting point of voids and cracks during hole expansion tests, V bending tests, U bending + close bending tests, and V bending + orthogonal VDA bending tests, so there is a situation where the desired λ, R / t, ST, and SFmax cannot be obtained. Therefore, in the case of containing Zr, the Zr content is preferably set to 0.1000% or less.

[0166] The Zr content is more preferably 0.0300% or less, and further preferably 0.0100% or less.

[0167] Ca: 0.0200% or less

[0168] Ca exists in the steel as inclusions. Here, when the Ca content is greater than 0.0200%, there is a situation where a large number of coarse inclusions are generated. In such a case, overly coarse precipitates and inclusions become the starting point of voids and cracks during hole expansion tests, V bending tests, U bending + close bending tests, or V bending + orthogonal VDA bending tests, so there is a situation where the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, in the case of containing Ca, the Ca content is preferably set to less than 0.0200%. The Ca content is preferably less than 0.0020%. The Ca content is more preferably less than 0.0019%, and further preferably less than 0.0018%. It should be noted that the lower limit of the Ca content is not particularly limited, but the Ca content is preferably more than 0.0005%. In addition, due to production technology limitations, the Ca content is more preferably more than 0.0010%.

[0169] Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, and REM: 0.0200% or less

[0170] Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are all elements effective for improving the hole expandability and bendability of the steel plate. In order to obtain such effects, the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are preferably set to 0.0001% or more, respectively.

[0171] On the other hand, when the content of Se, Te, Ge, Sr, Cs, Hf, Pb, Bi and REM is greater than 0.0200% or the content of As is greater than 0.0500%, a large amount of coarse precipitates and inclusions are generated. In such a case, the coarse precipitates and inclusions become the starting point of voids and cracks during the hole expansion test, V bending test, U bending + close bending test or V bending + orthogonal VDA bending test, so the desired λ, R / t, ST and SFmax cannot be obtained. Therefore, in the case of containing at least one of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM, the content of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM is preferably set to 0.0200% or less, and the content of As is preferably set to 0.0500% or less.

[0172] The Se content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Se content is more preferably 0.0180% or less, and further preferably 0.0150% or less.

[0173] The Te content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Te content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0174] The Ge content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Ge content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0175] The As content is more preferably 0.0010% or more, and even more preferably 0.0015% or more. The As content is more preferably 0.0400% or less, and even more preferably 0.0300% or less.

[0176] The Sr content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Sr content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0177] The Cs content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Cs content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0178] The Hf content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Hf content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0179] The Pb content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Pb content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0180] The Bi content is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The Bi content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0181] The REM is more preferably 0.0005% or more, and even more preferably 0.0008% or more. The REM is more preferably 0.0180% or less, and even more preferably 0.0150% or less.

[0182] It should be noted that the REM described in the present invention refers to scandium (Sc) with an atomic number of 21, yttrium (Y) with an atomic number of 39, and lanthanide elements from lanthanum (La) with an atomic number of 57 to lutetium (Lu) with an atomic number of 71. The REM concentration in the present invention refers to the total content of one or more elements selected from the above REM.

[0183] REM is not particularly limited, but Sc, Y, Ce, and La are preferred.

[0184] Steel structure

[0185] Next, the steel structure of the base steel plate of the steel plate according to one embodiment of the present invention will be described.

[0186] Area ratio of ferrite: 20.0% or more and 80.0% or less

[0187] Soft ferrite is a phase that improves ductility. It is also a necessary phase for generating isolated island-shaped fresh martensite, isolated island-shaped residual austenite, and suppressing the connection of voids and the expansion of cracks in the grains. In order to take into account the desired ductility and good λ, R / t, ST and SFmax, the area ratio of ferrite is set to be above 20.0%. On the other hand, when the area ratio of ferrite is excessively increased, it is difficult to make TS above 780MPa. In addition, it also leads to a decrease in YS and YR. Therefore, the area ratio of ferrite is set to be below 80.0%. In addition, the area ratio of ferrite is preferably above 30.0%.

[0188] Area ratio of fresh martensite: 15.0% or less (including 0.0%)

[0189] In the present invention, when the area ratio of fresh martensite increases excessively, the fresh martensite becomes the starting point of void generation during the hole expansion process of the hole expansion test or the bending process of the V-bending test, so the desired λ and R / t cannot be obtained. Therefore, the area ratio of fresh martensite is set to be less than 15.0%. In addition, the area ratio of fresh martensite is preferably less than 10.0%. It should be noted that there is no particular restriction on the lower limit of the area ratio of fresh martensite, and it can be 0.0%. The fresh martensite described here is martensite in a quenched state (not tempered). In addition, the fresh martensite described here also includes (isolated) island-shaped fresh martensite in the ferrite grains described later.

[0190] Area ratio of retained austenite: 3.0% or less (including 0.0%)

[0191] In the present invention, when the area ratio of retained austenite is excessively increased, when the steel plate is subjected to punching in the hole expansion test, when subjected to U bending in the U bending + close bending test, or when subjected to V bending in the V bending + orthogonal VDA test, hard fresh martensite generated by the processing induced phase transformation of the retained austenite is generated, and the generation of voids and the expansion of cracks occur in subsequent tests, and the desired λ, ST and SFmax cannot be obtained. Therefore, the area ratio of retained austenite is set to 3.0% or less. The area ratio of retained austenite is preferably 2.5% or less, and more preferably 2.0% or less. The lower limit of the area ratio of retained austenite is not particularly limited, but is preferably 0.1% or more, and more preferably 0.2% or more.

[0192] The retained austenite mentioned here also includes (isolated) island-shaped retained austenite in ferrite grains described later.

[0193] Here, in the second cooling step in the manufacturing method described later, a pressure of 2.0 kgf / mm2 is applied to the steel sheet in a temperature range of 300°C to 450°C. 2 The steel plate is subjected to a tension of the abovementioned amount, and then, the steel plate is passed through more than 5 passes while being brought into contact with a roll having a diameter of not less than 500 mm and not more than 1500 mm for 1 / 4 of a circle of the roll in each pass, thereby causing the untransformed austenite to undergo a processing-induced transformation into fresh martensite, and in a subsequent reheating step, the fresh martensite is tempered, and ultimately the area ratio of the fresh martensite is controlled to be less than 15.0%, and the volume ratio of the retained austenite to be less than 3.0%, thereby ensuring the desired area ratio of tempered martensite.

[0194] The value obtained by dividing the total area ratio of island-shaped fresh martensite and island-shaped retained austenite in the ferrite grains by the total area ratio of fresh martensite and retained austenite in the entire steel sheet: 0.65 or more

[0195] In the present invention, Figure 1 As shown, the isolated island-shaped fresh martensite (M') and the isolated island-shaped retained austenite (RA') in the ferrite (F) grains are finer than the tempered martensite (TM) and the hard second phase (fresh martensite (M) + retained austenite (RA)) existing in the ferrite grain boundary. Although they can become the formation position of voids, they are not easy to participate in the connection of voids and the expansion of cracks. They are necessary structures to obtain the desired λ, R / t, ST and SFmax while ensuring a TS of more than 780 MPa. Therefore, the value ((M'+RA') / (M+RA)) obtained by dividing the total area ratio of the isolated island-shaped fresh martensite and the isolated island-shaped retained austenite in the ferrite grains by the total area ratio of the fresh martensite and the retained austenite is set to be greater than 0.65.

[0196] It should be noted that, in the present invention, the value obtained by dividing the sum of the area ratios of isolated island-shaped fresh martensite and isolated island-shaped retained austenite in the ferrite grains by the sum of the area ratios of fresh martensite and retained austenite can be set to the value obtained by dividing the sum of the area ratios of island-shaped fresh martensite and island-shaped retained austenite in the ferrite grains by the sum of the area ratios of fresh martensite and retained austenite in the entire steel plate. That is, in the present invention, the value obtained by dividing the sum of the area ratios of island-shaped fresh martensite and island-shaped retained austenite in the ferrite grains by the sum of the area ratios of fresh martensite and retained austenite in the entire steel plate is set to 0.65 or more.

[0197] Furthermore, the value obtained by dividing the total area ratio of island-shaped fresh martensite and island-shaped retained austenite in the ferrite grains by the total area ratio of fresh martensite and retained austenite in the entire steel sheet is preferably 0.70 or more.

[0198] There is no particular upper limit on the value obtained by dividing the total area ratio of island fresh martensite and island retained austenite in the ferrite grains by the total area ratio of fresh martensite and volume ratio of retained austenite in the entire steel plate, but the value is preferably set to 0.94 or less, more preferably set to 0.92 or less.

[0199] Area ratio of bainite and tempered bainite: 10.0% or less (including 0.0%)

[0200] When the area ratio of bainite generated in the first cooling step and tempered bainite obtained by tempering the bainite generated in the reheating step increases excessively, the desired area ratio of tempered martensite cannot be obtained, and it is difficult to ensure a TS of 780 MPa or more. Therefore, the area ratio of bainite and tempered bainite (B+BT) is set to 10.0% or less. In addition, the area ratio of bainite and tempered bainite is preferably 8.0% or less. The area ratio of bainite and tempered bainite may be 0.0%.

[0201] Area ratio of tempered martensite: 10.0% or more and 70.0% or less

[0202] The hard second phase (fresh martensite + retained austenite) present at the ferrite grain boundary is a structure that promotes the formation of voids and the expansion of cracks during stamping and collision. On the other hand, tempered martensite is a structure that is mostly present at the ferrite grain boundary and is obtained by applying 2.0 kgf / mm2 to the steel sheet in the temperature range of 300°C to 450°C during the second cooling step in the manufacturing method described below. 2The steel sheet is subjected to a tension of more than 1000 mm and then passed through more than 5 passes while being in contact with a roll having a diameter of 500 mm or more and 1500 mm or less for 1 / 4 of the roll per pass, thereby causing the untransformed austenite to undergo a processing-induced transformation and become fresh martensite, and the fresh martensite is tempered in the subsequent reheating process. The tempered martensite is a necessary structure for obtaining the desired λ, R / t, ST and SFmax. Therefore, the area ratio of the tempered martensite is set to be 10.0% or more. The area ratio of the tempered martensite is preferably 20.0% or more.

[0203] On the other hand, if the area ratio of tempered martensite increases excessively, the desired area ratio of ferrite cannot be obtained, and the desired ductility cannot be ensured. Therefore, the area ratio of tempered martensite is set to 70.0% or less. The area ratio of tempered martensite is preferably 60.0% or less.

[0204] Average grain size of island-shaped fresh martensite and island-shaped retained austenite in ferrite grains: 2.0 μm or less

[0205] In the present invention, when the average grain size of the island-shaped fresh martensite and the island-shaped retained austenite in the ferrite grains is small, a TS of more than 780 MPa can be ensured and the formation of voids can be further suppressed, so that better λ, R / t, ST and SFmax can be obtained. Therefore, the average grain size of the island-shaped fresh martensite and the island-shaped retained austenite (M'+RA') in the ferrite grains is set to less than 2.0 μm. It should be noted that the average grain size of the island-shaped fresh martensite and the island-shaped retained austenite in the ferrite grains is preferably less than 1.0 μm.

[0206] The lower limit is not particularly limited, but the average grain size of the island-like fresh martensite and the island-like retained austenite in the ferrite grains is preferably 0.1 μm or more, more preferably 0.2 μm or more.

[0207] It should be noted that the area ratio of the remaining structure other than the above-mentioned ferrite, fresh martensite, retained austenite, bainite, tempered bainite, and tempered martensite is preferably set to 10.0% or less. The area ratio of the remaining structure is more preferably 5.0% or less. In addition, the area ratio of the remaining structure may be 0.0%.

[0208] The remaining structure is not particularly limited, and examples thereof include carbides such as pearlite and cementite, and unrecrystallized ferrite. The type of the remaining structure can be confirmed by, for example, observation using a SEM (Scanning Electron Microscope).

[0209] Here, the area ratios of ferrite, bainite, tempered bainite, tempered martensite, and hard second phase (fresh martensite+retained austenite) were measured as follows at a position of 1 / 4 of the plate thickness of the base steel plate.

[0210] That is, the sample is cut out in such a way that the plate thickness section (L section) parallel to the rolling direction of the steel plate becomes the observation surface. Then, the observation surface of the sample is ground using diamond abrasive paste, and then, fine grinding is performed using aluminum oxide. Then, the observation surface of the sample is etched using 3 volume % nitric acid ethanol solution to expose the structure. Then, the 1 / 4 position of the plate thickness of the steel plate is used as the observation position, and 5 fields of view are observed using SEM at a magnification of 3000 times. According to the obtained organizational image, Adobe Photoshop of Adobe Systems is used to calculate the area ratio obtained by dividing the area of ​​each constituent organization (ferrite, bainite, tempered bainite, tempered martensite and hard second phase (fresh martensite + residual austenite)) of 5 fields of view by the measured area, and these values ​​are averaged as the area ratio of each organization.

[0211] Ferrite: The black area is blocky in shape. There are almost no carbides inside. In addition, isolated islands of fresh martensite and isolated islands of retained austenite in ferrite grains are not included in the area ratio of ferrite.

[0212] Bainite and tempered bainite: appear in areas ranging from black to dark gray, and are blocky, amorphous, etc. Also, they contain relatively few carbides.

[0213] Tempered martensite: It is a gray area with an amorphous shape and contains a large number of carbides.

[0214] Hard second phase (retained austenite + fresh martensite): appears in a white to light gray area, and is amorphous. Also, it does not contain carbides.

[0215] Carbides: white areas in the form of dots and lines, enclosed in bainite, tempered bainite and tempered martensite.

[0216] Residual structure: The above-mentioned pearlite, cementite, etc. can be mentioned, and their morphologies and the like are well known.

[0217] From the SEM image used in the above-mentioned microstructure fraction measurement, the average area is calculated by dividing the total area of ​​the isolated island-like fresh martensite and the isolated island-like retained austenite in the ferrite grains by the number of the isolated island-like fresh martensite and the isolated island-like retained austenite in the ferrite grains. The above-mentioned average area is divided by pi, and the square root is multiplied by 2. The equivalent circle diameter thus obtained is taken as the average grain size.

[0218] In addition, the isolated island-shaped fresh martensite or isolated island-shaped retained austenite in one ferrite grain is measured as one island-shaped region which is surrounded by ferrite on the periphery and formed integrally without interruption in the SEM image.

[0219] In addition, the area ratio of retained austenite was measured as follows.

[0220] That is, the base steel plate is mechanically ground along the plate thickness direction (depth direction) to 1 / 4 of the plate thickness, and then chemically polished with oxalic acid to form an observation surface. Next, the observation surface is observed using the X-ray diffraction method. Using MoKα rays as incident X-rays, the diffraction intensity of each surface of fcc iron (austenite) (200), (220) and (311) is calculated relative to the diffraction intensity of each surface of bcc iron (200), (211) and (220), and the volume ratio of retained austenite is calculated from the ratio of the diffraction intensity of each surface. In addition, it is considered that the retained austenite is three-dimensionally homogeneous, and the volume ratio of retained austenite is taken as the area ratio of retained austenite.

[0221] The area ratio of fresh martensite is determined by subtracting the area ratio of retained austenite from the area ratio of the hard second phase determined as described above.

[0222] [Area ratio of fresh martensite (%)] = [Area ratio of hard second phase (%)] - [Area ratio of retained austenite (%)]

[0223] The area ratio of the remaining structure is obtained by subtracting the area ratio of ferrite, the area ratio of bainite and tempered bainite, the area ratio of tempered martensite, and the area ratio of the hard second phase obtained as described above from 100.0%.

[0224] [Area ratio of remaining structure (%)] = 100.0 - [Area ratio of ferrite (%)] - [Area ratio of bainite and tempered bainite (%)] - [Area ratio of tempered martensite (%)] - [Area ratio of hard second phase (%)]

[0225] Diffusible hydrogen content in the base steel sheet (in the steel): 0.50 mass ppm or less

[0226] When the amount of diffusible hydrogen in the steel sheet exceeds 0.50 mass ppm, desired λ, R / t, ST and SFmax cannot be obtained.

[0227] It should be noted that the amount of diffusible hydrogen in the steel sheet is preferably set to 0.25 mass ppm or less. In addition, the lower limit of the amount of diffusible hydrogen in the steel sheet is not particularly limited, but due to production technology limitations, the amount of diffusible hydrogen in the steel sheet is preferably set to 0.01 mass ppm or more.

[0228] It should be noted that the base steel plate for measuring the amount of diffusible hydrogen may be a high-strength steel plate before plating or a high-strength galvanized steel plate after galvanizing and before processing. In addition, the base steel plate may be a steel plate subjected to punching, stretch flange forming, or the like after galvanizing, or may be a base portion of a product manufactured by welding the processed steel plate.

[0229] Here, the method for determining the amount of diffusible hydrogen in the steel plate is as follows. A test piece with a length of 30 mm and a width of 5 mm is cut. When a zinc coating is formed on the steel plate, the hot-dip galvanized layer or the alloyed hot-dip galvanized layer is removed with an alkali. Then, the amount of hydrogen released from the test piece is determined by thermal desorption analysis. Specifically, the test piece is continuously heated from room temperature (-5 to 55°C) to 300°C at a heating rate of 200°C / hour, and then cooled to room temperature, and the cumulative amount of hydrogen released from the test piece in the range from room temperature to 210°C is measured as the amount of diffusible hydrogen in the steel plate. The determination of the amount of diffusible hydrogen is preferably carried out after the manufacture of the steel plate is completed. It should be noted that the determination of the amount of hydrogen is more preferably carried out within 1 week after the manufacture of the steel plate is completed. It should be noted that the room temperature is set within the range of local temperature changes within 1 year in consideration of production in various countries around the world. Usually, it is preferably in the range of 10 to 50°C.

[0230] Surface soft layer

[0231] The base steel plate of the steel plate according to one embodiment of the present invention preferably has a surface soft layer on the surface of the base steel plate. Since the surface soft layer helps to suppress the extension of bending cracks during stamping and vehicle body collision, the bending fracture resistance is further improved. It should be noted that the surface soft layer refers to a decarburized layer, which is a surface area with a Vickers hardness of less than 85% relative to the Vickers hardness of the cross section at a position of 1 / 4 of the plate thickness.

[0232] Here, the surface soft layer is formed in an area 200 μm or less from the surface of the base steel plate in the plate thickness direction. The area where the surface soft layer is formed is preferably 150 μm or less, more preferably 120 μm or less from the surface of the base steel plate in the plate thickness direction. It should be noted that there is no particular lower limit on the thickness of the surface soft layer, but it is preferably 8 μm or more, more preferably greater than 17 μm. In addition, the surface soft layer is preferably 30 μm or more, more preferably 40 μm or more.

[0233] The 1 / 4 position of the plate thickness of the base steel plate for measuring the Vickers hardness is a non-surface soft layer (a layer that does not satisfy the hardness condition of the surface soft layer specified in the present invention).

[0234] The Vickers hardness was measured at a load of 10 gf in accordance with JIS Z 2244-1 (2020).

[0235] Nanohardness of the soft surface layer

[0236] When the nanohardness of 300 or more points is measured in an area of ​​50 μm×50 μm on the plate surface at each of the position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate and the position 1 / 2 of the depth in the plate thickness direction, the ratio of the number of measurements of the plate surface having a nanohardness of 7.0 GPa or more at the position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 0.10 or less relative to the total number of measurements at the position 1 / 4 of the depth in the plate thickness direction of the surface soft layer

[0237] In the present invention, in order to obtain excellent bendability during stamping and excellent bending fracture characteristics during collision, it is preferred that when the nanohardness of more than 300 points is measured in the 50μm×50μm area of ​​the plate surface at each position of 1 / 4 position of the plate thickness direction depth of the surface soft layer and 1 / 2 position of the plate thickness direction depth from the base steel plate surface, the nanohardness of the plate surface at the position of 1 / 4 position of the plate thickness direction depth of the surface soft layer from the base steel plate surface is 7.0GPa or more, and the total measured number of the position of 1 / 4 position of the plate thickness direction depth of the surface soft layer is less than 0.10. When the ratio of nanohardness of more than 7.0GPa is less than 0.10, it means that the ratio of hard tissue (martensite, etc.), inclusions, etc. is small, and the generation, connection, and expansion of cracks of hard tissue (martensite, etc.), inclusions, etc. during stamping and collision can be further suppressed, and excellent R / t and SFmax can be obtained.

[0238] The standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the steel plate surface is 1.8 GPa or less, and the standard deviation σ of the nanohardness of the plate surface at a position 1 / 2 of the depth in the plate thickness direction of the surface soft layer from the steel plate surface is 2.2 GPa or less

[0239] In the present invention, in order to obtain excellent bendability during stamping and excellent bending fracture characteristics during collision, it is preferred that the standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the depth in the thickness direction of the surface soft layer from the surface of the steel plate is 1.8 GPa or less, and the standard deviation σ of the nanohardness of the plate surface at a position 1 / 2 of the depth in the thickness direction of the surface soft layer from the surface of the steel plate is 2.2 GPa or less. When the standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the depth in the thickness direction of the surface soft layer from the surface of the steel plate is 1.8 GPa or less, and the standard deviation σ of the nanohardness of the plate surface at a position 1 / 2 of the depth in the thickness direction of the surface soft layer from the surface of the steel plate is 2.2 GPa or less, it means that the difference in tissue hardness in the microscopic area is small, which can further inhibit the generation, connection and expansion of cracks during stamping and collision, and can obtain excellent R / t and SFmax.

[0240] In addition, the preferred range of the standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the plate thickness direction depth of the surface soft layer from the base steel plate surface is preferably 1.7 GPa or less. The standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the plate thickness direction depth of the surface soft layer from the base steel plate surface is more preferably 1.3 GPa or less. The lower limit is not particularly limited, but the standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the plate thickness direction depth of the surface soft layer from the base steel plate surface can be set to 0.5 GPa or more.

[0241] The more preferred range of the standard deviation σ of the nanohardness of the plate surface at 1 / 2 of the plate thickness direction depth of the surface soft layer from the base steel plate surface is 2.1 GPa or less. The standard deviation σ of the nanohardness of the plate surface at 1 / 2 of the plate thickness direction depth of the surface soft layer from the base steel plate surface is more preferably 1.7 GPa or less. The lower limit is not particularly limited, but the standard deviation σ of the nanohardness of the plate surface at 1 / 2 of the plate thickness direction depth of the surface soft layer from the base steel plate surface can be set to 0.6 GPa or more.

[0242] Here, the nanohardness of the plate surface at the 1 / 4 position and the 1 / 2 position in the depth in the plate thickness direction refers to the hardness measured by the following method.

[0243] First, in the case where a coating is formed, after the coating is peeled off, mechanical grinding is performed until the position of 1 / 4 of the depth in the thickness direction of the surface soft layer from the surface of the base steel plate to the position of 5 μm, polishing with diamond and alumina is performed until the position of 1 / 4 of the depth in the thickness direction of the surface soft layer from the surface of the base steel plate, and further colloidal silica grinding is performed. Here, the coating to be peeled off is the zinc coating when the zinc coating is formed, the metal coating when the metal coating is formed, and the zinc coating and the metal coating when the zinc coating and the metal coating are formed.

[0244] The nanohardness was measured using Tribo-950 manufactured by Hysitron Corporation and a Berkovich-shaped diamond indenter under the following conditions: load: 500 μN, measurement area: 50 μm×50 μm, and dot spacing: 2 μm.

[0245] In addition, mechanical grinding, polishing with diamond and alumina, and further colloidal silica grinding were performed until the surface soft layer reached 1 / 2 of the depth in the thickness direction. Then, the nanohardness was measured using Hysitron's Tribo-950 with a Berkovich-shaped diamond indenter under the conditions of load: 500 μN, measurement area: 50 μm×50 μm, and dot interval: 2 μm.

[0246] Nanohardness was measured at 300 or more points at 1 / 4 of the depth in the plate thickness direction, and nanohardness was also measured at 300 or more points at 1 / 2 of the depth in the plate thickness direction.

[0247] For example, when the thickness of the surface soft layer is 100 μm, the 1 / 4 position is 25 μm from the surface of the surface soft layer, and the 1 / 2 position is 50 μm from the surface of the surface soft layer. The nanohardness of more than 300 points is measured at the 25 μm position, and the nanohardness of more than 300 points is also measured at the 50 μm position.

[0248] Metal plating (first layer)

[0249] In addition, the steel sheet according to one embodiment of the present invention preferably has a metal coating (first coating, pre-coating) on ​​one or both surfaces of the base steel sheet (it should be noted that the metal coating (first coating) does not include a hot-dip galvanized layer or a zinc coating of an alloyed hot-dip galvanized layer). The metal coating is preferably a metal electroplating layer, and the metal electroplating layer is used as an example for explanation below.

[0250] By forming a metal plating layer on the surface of the steel sheet, the metal plating layer on the outermost surface helps to suppress the occurrence of bending cracks during press forming and vehicle body collision, thereby further improving the bending fracture resistance.

[0251] In the present invention, by setting the dew point to be higher than -20°C, the thickness of the soft layer can be further increased, and the shaft crushing characteristics can be made very excellent. In this regard, in the present invention, by having a metal plating layer, even if the dew point is below -20°C and the thickness of the soft layer is small, the shaft crushing characteristics equivalent to those when the thickness of the soft layer is large can be obtained.

[0252] The metal type of the metal plating layer can be any one of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi, and more preferably Fe. Hereinafter, the Fe-based plating layer will be described as an example, but the following conditions for Fe can also be adopted for other metal types.

[0253] The coating weight of the Fe-based electroplating layer is set to be greater than 0 g / m 2 , preferably set to 2.0g / m 2 There is no particular upper limit on the amount of Fe-based electroplating layer deposited on each side, but from a cost perspective, it is preferred that the amount of Fe-based electroplating layer deposited on each side be set to 60 g / m 2 The Fe-based electroplating layer is preferably set to a weight of 50 g / m 2 Below, more preferably set to 40g / m 2 Below, it is further preferably set to 30g / m 2 the following.

[0254] The adhesion amount of the Fe-based electroplated layer is measured as follows. A sample of 10×15 mm in size is cut from the Fe-based electroplated steel plate, embedded in a resin, and made into a cross-section embedded sample. Use a scanning electron microscope (SEM) with an acceleration voltage of 15 kV and a magnification of 2000 to 10000 times according to the thickness of the Fe-based plating layer to observe any three places of the cross section, and multiply the average value of the thickness of the three fields of view by the specific gravity of iron, thereby converting it into the adhesion amount of each single side of the Fe-based electroplated layer.

[0255] As Fe system electroplating layer, except pure Fe can be used, alloy plating layers such as Fe-B alloy, Fe-C alloy, Fe-P alloy, Fe-N alloy, Fe-O alloy, Fe-Ni alloy, Fe-Mn alloy, Fe-Mo alloy, Fe-W alloy can also be used.The composition of Fe system electroplating layer is not particularly limited, but preferably set to contain one or more elements selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V and Co below 10 mass %, the remainder is made of Fe and inevitable impurities.By setting the amount of the element except Fe to total below 10 mass %, the reduction of electrolysis efficiency can be prevented, and Fe system electroplating layer can be formed at low cost.In the case of Fe-C alloy, the content of C is preferably set to below 0.08 mass %.

[0256] Next, the mechanical properties of the steel sheet according to one embodiment of the present invention will be described.

[0257] Tensile strength (TS): 780MPa or more

[0258] The tensile strength of the steel sheet according to one embodiment of the present invention is 780 MPa or more.

[0259] It should be noted that the yield stress (YS), yield ratio (YR), total elongation (El), limit hole expansion ratio (λ), limit spacer thickness (ST) in U bending + close bending test and stroke (SFmax) at maximum load in V bending + orthogonal VDA bending test of the steel plate according to one embodiment of the present invention, as well as the presence or absence of fracture (appearance crack) in the axial crush test are as described above.

[0260] In addition, the tensile strength (TS), yield stress (YS), yield ratio (YR) and total elongation (El) are measured by a tensile test based on JIS Z 2241 (2011) described later in the examples. The limiting hole expansion ratio (λ) is measured by a hole expansion test based on JIS Z 2256 (2020) described later in the examples. The limiting spacer thickness (ST) is measured by a U-bend + close-fitting bend test described later in the examples. The stroke (SFmax) at the maximum load in the V-bend + orthogonal VDA bend test is measured by the V-bend + orthogonal VDA bend test described later in the examples. Whether there is a break (appearance crack) in the axial crush test is measured by the axial crush test described later in the examples.

[0261] Zinc coating (second coating)

[0262] The steel sheet according to one embodiment of the present invention may have a zinc coating formed on a base steel sheet (on the surface of the base steel sheet or on the surface of the metal coating when a metal coating is formed) as the outermost layer, and the zinc coating may be provided on only one surface of the base steel sheet or on both surfaces. The steel sheet having the zinc coating may be a galvanized steel sheet.

[0263] That is, the steel sheet of the present invention may have a base steel sheet and a second coating (zinc coating, aluminum coating, etc.) formed on the base steel sheet. Alternatively, the steel sheet may have a base steel sheet and a metal coating (a first coating (excluding the zinc coating, i.e., the second coating)) and a second coating (zinc coating, aluminum coating, etc.) sequentially formed on the base steel sheet.

[0264] It should be noted that the zinc plating layer mentioned here refers to a plating layer containing Zn as a main component (Zn content is 50.0% or more), and examples thereof include a hot-dip galvanized layer and an alloyed hot-dip galvanized layer.

[0265] Here, the hot-dip galvanized layer is preferably composed of, for example, Zn and 20.0% by mass or less of Fe, and 0.001% by mass or more and 1.0% by mass or less of Al. In addition, the hot-dip galvanized layer may optionally contain a total of 0.0% by mass or more and 3.5% by mass or less of one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi and REM. In addition, the Fe content of the hot-dip galvanized layer is more preferably less than 7.0% by mass. It should be noted that the remainder other than the above elements is an inevitable impurity.

[0266] In addition, the alloyed hot-dip galvanneal layer is preferably composed of, for example, less than 20% by mass of Fe, more than 0.001% by mass and less than 1.0% by mass of Al. In addition, in the alloyed hot-dip galvanneal layer, one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi and REM may be optionally contained in a total of more than 0.0% by mass and less than 3.5% by mass. The Fe content of the alloyed hot-dip galvanneal layer is more preferably more than 7.0% by mass, and more preferably more than 8.0% by mass. In addition, the Fe content of the alloyed hot-dip galvanneal layer is more preferably less than 15.0% by mass, and more preferably less than 12.0% by mass. It should be noted that the remainder other than the above-mentioned elements is an inevitable impurity.

[0267] The coating weight per single side of the zinc coating is not particularly limited, but is preferably set to 20 g / m 2 In addition, the coating weight per single side of the zinc coating is preferably set to 80 g / m 2 the following.

[0268] In addition, the coating adhesion amount of the zinc plating layer was measured as follows.

[0269] That is, a treatment solution was prepared by adding 0.6 g of a corrosion inhibitor for Fe (manufactured by Asahi Chemical Industry Co., Ltd., "IBIT 700BK" (registered trademark)) to 1 L of a 10% by mass hydrochloric acid aqueous solution. Next, the steel plate as the test material was immersed in the treatment solution to dissolve the zinc coating. Then, the mass reduction of the test material before and after dissolution was measured, and the value was divided by the surface area of ​​the base steel plate (the surface area of ​​the portion covered by the coating), thereby calculating the coating adhesion (g / m 2 ).

[0270] It should be noted that the plate thickness of the steel plate according to one embodiment of the present invention is not particularly limited, but is preferably 0.5 mm or more.

[0271] The plate thickness is more preferably greater than 0.8 mm. The plate thickness is more preferably 0.9 mm or more. The plate thickness is more preferably 1.0 mm or more. The plate thickness is more preferably 1.2 mm or more.

[0272] In addition, the thickness of the steel plate is preferably 3.5 mm or less, and more preferably 2.3 mm or less.

[0273] The width of the steel plate of the present invention is not particularly limited, but is preferably set to 500 mm or more, more preferably 750 mm or more. The width of the steel plate is preferably set to 1600 mm or less, more preferably 1450 mm or less.

[0274] [2. Method for manufacturing steel plate]

[0275] Next, a method for producing a steel sheet according to an embodiment of the present invention will be described.

[0276] The method for manufacturing a steel plate of the present invention comprises: a hot rolling step, wherein a steel slab having the above-mentioned composition is hot rolled at a finishing rolling temperature of 820° C. or higher to obtain a hot rolled steel plate; a heating step, wherein the steel plate after the hot rolling step is heated at an average heating rate of 7° C. / second or higher in a temperature range of 350° C. to 600° C. or lower; an annealing step, wherein annealing is performed at an annealing temperature of 750° C. to 900° C. and an annealing time of 20 seconds or higher; a first cooling step, wherein cooling is performed at an average cooling rate of 7° C. / second or higher from (annealing temperature-30° C.) to 650° C. and an average cooling rate of 14° C. / second or lower from 650° C. to 500° C. after the annealing step; and a second cooling step, wherein a heat treatment temperature of 2.0 kgf / mm2 is applied to the steel plate at a temperature range of 300° C. to 450° C. or lower after the first cooling step. 2 The steel plate is subjected to a tension of at least 500 mm and at most 1500 mm, and then passed through more than 5 passes while making the steel plate contact with a roll having a diameter of at least 500 mm and at most 1500 mm for 1 / 4 of a roll circle in each pass, and then cooled to a cooling stop temperature of less than 250°C; and a reheating process, wherein after the second cooling process, the steel plate is reheated to a temperature range of not less than the cooling stop temperature and not more than 440°C and maintained for more than 20 seconds, or, further comprising a cold rolling process of subjecting the steel plate after the hot rolling process and before the heating process to cold rolling with a reduction rate of not less than 20% and not more than 80% to obtain a cold-rolled steel plate.

[0277] In the present invention, the melting method of the steel raw material (steel billet) is not particularly limited, and any known melting method such as a converter, an electric furnace, etc. is suitable. In addition, in order to prevent macrosegregation, the steel billet (steel billet) is preferably manufactured by a continuous casting method, but it can also be manufactured by an ingot casting method, a thin slab casting method, etc. In addition, in addition to the existing method of temporarily cooling to room temperature after manufacturing the steel billet and then heating it again, energy-saving processes such as direct rolling and direct rolling can be applied without problem, in which the steel billet is directly loaded into a heating furnace in a warm sheet state without cooling to room temperature, or rolling is performed immediately after a slight heat preservation.

[0278] (Hot rolling process)

[0279] When heating the steel slab, the steel slab heating temperature is preferably set to 1100° C. or higher from the viewpoint of melting carbides and reducing rolling load. In addition, in order to prevent an increase in scale loss, the steel slab heating temperature is preferably set to 1300° C. or lower.

[0280] It should be noted that the billet heating temperature is the temperature of the billet surface. In addition, the billet is made into a thin slab by rough rolling under normal conditions, but when the heating temperature is lowered, from the viewpoint of preventing failure during hot rolling, it is preferred to heat the thin slab using a rod heater or the like before finish rolling.

[0281] Finishing temperature: above 820℃

[0282] Finish rolling increases the rolling load, increases the reduction rate in the non-recrystallized state of austenite, and develops an abnormal structure that is elongated in the rolling direction, resulting in a decrease in the ductility, hole expansion, and bendability of the final material. Therefore, the finish rolling temperature is set to 820°C or more. The finish rolling temperature is preferably 830°C or more, and more preferably 850°C or more. In addition, the finish rolling temperature is preferably 1080°C or less, and more preferably 1050°C or less.

[0283] In addition, there is no particular restriction on the coiling temperature after hot rolling, but it is necessary to consider the reduction of ductility, hole expansion and bendability of the final material. Therefore, the coiling temperature after hot rolling is preferably set to 300°C or more. In addition, the coiling temperature after hot rolling is preferably set to 700°C or less.

[0284] It should be noted that the rough rolled sheets can be joined together and continuously finished during hot rolling. In addition, the rough rolled sheets can be temporarily coiled. In addition, in order to reduce the rolling load during hot rolling, part or all of the finishing rolling can also be set to lubrication rolling. From the perspective of uniformity of the shape of the steel plate and uniformity of the material, lubrication rolling is also effective. It should be noted that the friction coefficient during lubrication rolling is preferably set to 0.10 or more. In addition, the friction coefficient during lubrication rolling is preferably set to 0.25 or less.

[0285] (Pickling process)

[0286] The hot-rolled steel sheet manufactured as above may be pickled. Since pickling can remove oxides on the surface of the steel sheet, it can be performed to ensure good chemical conversion treatment and coating quality of the high-strength steel sheet as the final product. In addition, pickling can be performed once or in multiple times.

[0287] (Cold rolling process)

[0288] The hot-rolled pickled plate or hot-rolled steel plate obtained as above is subjected to cold rolling as required. In the case of cold rolling, the pickled plate can be directly subjected to cold rolling after hot rolling, or can be subjected to cold rolling after heat treatment. In addition, the cold-rolled steel plate obtained after cold rolling can also be subjected to pickling as desired.

[0289] The cold rolling is performed by multi-pass rolling requiring two or more passes, such as tandem multi-stand rolling or reverse rolling.

[0290] According to the needs, the cold rolling reduction rate is more than 20% and less than 80%

[0291] When cold rolling is performed, the cold rolling reduction rate (cumulative reduction rate) is not particularly limited, but is preferably set to be greater than 20% and less than 80%. When the cold rolling reduction rate is less than 20%, coarsening and non-uniformization of the steel structure are likely to occur in the annealing process, and the TS and bendability of the final product may be reduced. Therefore, the cold rolling reduction rate is preferably set to be greater than 20%. On the other hand, when the cold rolling reduction rate is greater than 80%, the shape of the steel sheet is likely to be poor, and the amount of zinc coating adhesion may become uneven. Therefore, the cold rolling reduction rate is preferably set to be less than 80%.

[0292] (Metal plating (electrometal plating, first plating) step)

[0293] In one embodiment of the present invention, a first plating step may be included in which a metal plating layer (first plating layer) is formed by plating one or both surfaces of a steel sheet after a hot rolling step (after a cold rolling step when cold rolling is performed) and before a heating step.

[0294] For example, the surface of the hot-rolled steel sheet or cold-rolled steel sheet obtained as above can be subjected to electroplating metal treatment to produce a pre-annealing electroplated metal steel sheet having a pre-annealing metal plating layer formed on at least one side. It should be noted that the metal plating mentioned here does not include zinc plating (second plating).

[0295] The electroplating metal treatment method is not particularly limited, but as described above, the metal plating layer formed on the base steel sheet is preferably a metal electroplating layer, and therefore, the electroplating metal treatment is preferably performed.

[0296] For example, the Fe-based electroplating bath may be a sulfuric acid bath, a hydrochloric acid bath, or a mixture of the two. In addition, the amount of metal plating layer attached before annealing can be adjusted according to the power-on time, etc. It should be noted that the metal-plated steel sheet before annealing means that the metal plating layer has not undergone an annealing process, and does not exclude the method of pre-annealing the hot-rolled steel sheet before the metal plating treatment, the pickling treatment plate after hot rolling, or the cold-rolled steel sheet.

[0297] Here, the metal type of the electroplating layer can be any one of Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Rt, Au, Hg, Ti, Pb, and Bi, and more preferably Fe. The Fe-based electroplating layer is used as an example for explanation below, but the following conditions for the Fe-based electroplating layer can also be used for other metal-based electroplating layers.

[0298] The Fe ion content in the Fe-based electroplating bath before power on is expressed as Fe 2+ The Fe ion content in the Fe-based electroplating bath is expressed as Fe 2+ When it is 0.5 mol / L or more, a sufficient Fe deposition amount can be obtained. In order to obtain a sufficient Fe deposition amount, the Fe ion content in the Fe-based electroplating bath before the start of energization is preferably set to 2.0 mol / L or less.

[0299] In addition, Fe ions and at least one element selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V and Co can be contained in the Fe-based electroplating bath. The total content of these elements in the Fe-based electroplating bath is preferably set in a manner that the total content of these elements in the Fe-based electroplating layer before annealing is less than 10% by mass. It should be noted that the metal element can be contained in the form of metal ions, and the non-metallic element can be contained as a part of boric acid, phosphoric acid, nitric acid, organic acid, etc. In addition, the iron sulfate plating solution can also contain conductive additives such as sodium sulfate and potassium sulfate, chelating agents, and pH buffers.

[0300] There are no special restrictions on other conditions of the Fe-based electroplating bath. Considering the constant temperature maintenance, the temperature of the Fe-based electroplating solution is preferably set to above 30°C, preferably below 85°C. There are no special restrictions on the pH of the Fe-based electroplating bath, but from the viewpoint of preventing the reduction of current efficiency caused by the generation of hydrogen, it is preferably set to above 1.0. In addition, considering the conductivity of the Fe-based electroplating bath, it is preferably below 3.0. Regarding the current density, from the viewpoint of productivity, it is preferably set to 10A / dm 2 From the viewpoint of easy control of the adhesion amount of the Fe-based electroplating layer, it is preferably set to 150 A / dm 2The sheet passing speed is preferably set to 5 mpm or more from the viewpoint of productivity, and is preferably set to 150 mpm or less from the viewpoint of stably controlling the amount of adhesion.

[0301] It should be noted that as a treatment before the Fe-based electroplating treatment, degreasing treatment and water washing for cleaning the surface of the steel plate, and pickling treatment and water washing for activating the surface of the steel plate can be implemented. Following these pretreatments, the Fe-based electroplating treatment is implemented. The methods of degreasing treatment and water washing are not particularly limited, and the usual methods can be used. In the pickling treatment, various acids such as sulfuric acid, hydrochloric acid, nitric acid and mixtures thereof can be used. Among them, sulfuric acid, hydrochloric acid or a mixture thereof is preferred. The concentration of the acid is not particularly limited, but if the ability to remove the oxide film and prevent surface roughness (surface defects) caused by excessive pickling are considered, 1 to 20% by mass is preferred. In addition, the pickling treatment solution may contain a defoaming agent, a pickling accelerator, a pickling inhibitor, and the like.

[0302] (Heating process)

[0303] In one embodiment of the present invention, the step includes heating the steel plate within a temperature range of not less than 350°C and not more than 600°C at an average heating rate of not less than 7°C / second after the hot rolling step (after the cold rolling step in the case of cold rolling, after the metal plating step in the case of metal plating to form a metal coating (first coating) layer, after the metal plating step, and after the metal plating step in the case of cold rolling and metal plating).

[0304] Average heating rate in the temperature range of 350°C or higher and 600°C or lower: 7°C / second or higher

[0305] In the present invention, by increasing the average heating rate in the temperature range of 350°C to 600°C, the ratio of isolated fine island-shaped hard second phase (martensite + retained austenite) in the ferrite grains is increased, thereby increasing λ, R / t, ST and SFmax. Therefore, the average heating rate in the temperature range of 350°C to 600°C is set to 7°C / s or more. Preferably, it is set to 9°C / s or more.

[0306] The upper limit is not particularly limited, but the average heating rate in the temperature range of 350° C. to 600° C. is preferably set to 100° C. / s or less, more preferably 90° C. / s or less.

[0307] Here, the average heating rate (° C. / s) can be calculated by (heating end temperature (° C.)−heating start temperature (° C.)) / heating time (s).

[0308] (Annealing process)

[0309] In one embodiment of the present invention, an annealing step is included in which annealing is performed under the conditions of an annealing temperature of 750° C. to 900° C. and an annealing time of 20 seconds or more after the temperature raising step.

[0310] Annealing temperature: above 750℃ and below 900℃

[0311] When the annealing temperature is lower than 750°C, the formation ratio of austenite during heating in the two-phase region of ferrite and austenite becomes insufficient. Therefore, the area ratio of ferrite increases excessively after annealing, and desired TS, YS, and YR cannot be obtained.

[0312] On the other hand, when the annealing temperature is higher than 900° C., an area ratio of ferrite of 20.0% or more cannot be obtained, and ductility decreases.

[0313] Therefore, the annealing temperature is set to be 750° C. or higher and 900° C. or lower. The annealing temperature is preferably 880° C. or lower. The annealing temperature is the highest temperature reached in the annealing step.

[0314] Annealing time: more than 20 seconds

[0315] When the annealing time is less than 20 seconds, the formation ratio of austenite in the heating of the two-phase region of ferrite and austenite becomes insufficient. Therefore, the area ratio of ferrite increases excessively after annealing, and TS, YS and YR cannot be obtained. Therefore, the annealing time is set to 20 seconds or more. The annealing time is preferably 30 seconds or more, and more preferably 50 seconds or more.

[0316] It should be noted that the upper limit of the annealing time is not particularly limited, but the annealing time is preferably set to 900 seconds or less, more preferably 800 seconds or less. The annealing time is further preferably 300 seconds or less, and further more preferably 220 seconds or less.

[0317] It should be noted that the annealing time refers to the holding time in the temperature range of (annealing temperature - 40 ° C) or more and below the annealing temperature. That is, the annealing time includes not only the holding time at the annealing temperature, but also the residence time in the temperature range of (annealing temperature - 40 ° C) or more and below the annealing temperature during heating and cooling before and after reaching the annealing temperature.

[0318] The number of annealing times may be two or more, but is preferably one time from the viewpoint of energy efficiency.

[0319] Dew point of annealing atmosphere (annealing atmosphere): -30°C or above

[0320] In one embodiment of the present invention, the dew point of the atmosphere (annealing atmosphere) in the annealing process is preferably set to -30°C or higher. By setting the dew point of the annealing atmosphere in the annealing process to -30°C or higher for annealing, the decarburization reaction can be promoted, and a deeper surface soft layer can be formed. The dew point of the annealing atmosphere in the annealing process is more preferably -25°C or higher, further preferably higher than -20°C, further more preferably -15°C or higher, and most preferably -5°C or higher.

[0321] The upper limit of the dew point of the annealing atmosphere in the annealing process is not particularly specified, but in order to appropriately prevent oxidation of the Fe-based electroplating layer surface and to provide good coating adhesion when the zinc coating layer is provided, the dew point of the annealing atmosphere in the annealing process is preferably set to 30° C. or less. The dew point of the annealing atmosphere in the annealing process is more preferably set to 25° C. or less, and further preferably set to 20° C. or less.

[0322] (First Cooling Step)

[0323] The present invention includes a first cooling step, wherein cooling is performed after the annealing step under conditions where the average cooling rate from (annealing temperature - 30°C) to 650°C is set to 7°C / sec or more and the average cooling rate from 650°C to 500°C is set to 14°C / sec or less.

[0324] Average cooling rate from (annealing temperature -30°C) to 650°C: 7°C / sec or more

[0325] In the present invention, when rapidly cooled in a high temperature region above 650°C, fine austenite remains at the ferrite grain boundary, and the ratio of isolated fine island-shaped hard second phase (martensite + retained austenite) in the final ferrite grain increases. Therefore, the average cooling rate from (annealing temperature -30°C) to 650°C is set to 7°C / second or more. The average cooling rate from (annealing temperature -30°C) to 650°C is preferably 9°C / second or more.

[0326] The average cooling rate from (annealing temperature - 30°C) to 650°C is preferably 80°C / sec or less, more preferably 60°C / sec or less. The average cooling rate is further preferably 30°C / sec or less, further more preferably 18°C / sec or less.

[0327] Here, the average cooling rate (° C. / s) can be calculated by (annealing temperature (° C.)-30 (° C.)-650 (° C.)) / cooling time (s).

[0328] Average cooling rate from 650°C to 500°C: less than 14°C / sec

[0329] In the present invention, when slowly cooled in the medium temperature region below 650°C, the fine austenite at the ferrite grain boundary merges with the adjacent ferrite with a close orientation to form a ferrite grain, and remains in the ferrite grain in the form of isolated fine island austenite, and finally the ratio of the isolated fine island hard second phase (martensite + residual austenite) in the ferrite grain increases. Therefore, the average cooling rate from 650°C to 500°C (the first cooling stop temperature) is 14°C / second or less, preferably 12°C / second or less. The average cooling rate from 650°C to 500°C is preferably 1°C / second or more, and more preferably 2°C / second or more.

[0330] Here, the average cooling rate (° C. / s) can be calculated by (650(° C.)-500(° C.)) / cooling time (s).

[0331] (Galvanizing step (second plating step))

[0332] In the present invention, the steel sheet may be subjected to galvanizing after the first cooling step. By performing the galvanizing, a galvanized steel sheet can be obtained.

[0333] Examples of the galvanizing treatment include hot-dip galvanizing and alloy galvanizing.

[0334] In the case of hot-dip galvanizing, it is preferred to immerse the steel sheet in a galvanizing bath at 440°C or higher and 500°C or lower, and then adjust the coating adhesion by gas wiping or the like. The hot-dip galvanizing bath is not particularly limited as long as the composition of the zinc coating can be obtained. For example, it is preferred to use a galvanizing bath having an Al content of 0.10% by mass or higher and the balance consisting of Zn and unavoidable impurities. The Al content is preferably 0.23% by mass or lower.

[0335] In the case of galvannealing, it is preferred that the galvannealing treatment be performed by heating the galvannealed steel sheet to an alloying temperature of 450° C. or higher after the galvannealing treatment as described above. The alloying temperature is preferably set to 600° C. or lower.

[0336] When the alloying temperature is lower than 450°C, the Zn-Fe alloying speed slows down, and alloying becomes difficult. On the other hand, when the alloying temperature is higher than 600°C, the untransformed austenite transforms to pearlite, and it is difficult to make TS above 780MPa. It should be noted that the alloying temperature is more preferably above 500°C, and more preferably above 510°C. In addition, the alloying temperature is more preferably below 570°C.

[0337] In addition, the coating weight of hot-dip galvanized steel sheet (GI) and alloyed hot-dip galvannealed steel sheet (GA) is preferably set to 20 g / m per single side. 2In addition, the coating weight per single side of the zinc coating is preferably set to 80 g / m 2 It should be noted that the coating adhesion amount can be adjusted by gas wiping or the like.

[0338] (Second Cooling Step)

[0339] The present invention includes a second cooling step, wherein after the first cooling step (after the galvanizing step in the case of the galvanizing step), a heat treatment of 2.0 kgf / mm2 is applied to the steel sheet in a temperature range of 300°C to 450°C. 2 The steel sheet is passed through 5 or more passes under the above tension while being brought into contact with a roll having a diameter of 500 mm to 1500 mm for 1 / 4 of the roll per pass, and then cooled to a cooling stop temperature (second cooling stop temperature) of 250° C. or less.

[0340] Tension applied within the temperature range of 300°C to 450°C: 2.0kgf / mm 2 above

[0341] In the present invention, the steel sheet is subjected to a 2.0 kgf / mm 2 With the above tension, most of the austenite is transformed into martensite due to the processing (stress, strain) induced phase transformation, and then tempered in the reheating process, so the area ratio of fresh martensite in the final structure can be reduced, and an appropriate amount of tempered martensite can be ensured. In addition, the amount of austenite just after the second cooling process can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, the desired λ, R / t, ST and SFmax can be obtained.

[0342] Here, the tension is calculated by dividing the total value of the load (kgf) of the load cells on the left and right sides of the roll by the cross-sectional area of ​​the steel plate (=plate thickness (mm) × plate width (mm)) (mm 2 It should be noted that the force sensor needs to be arranged parallel to the tension direction.

[0343] The load cell is preferably positioned 200 mm from both ends of the roll. The roll length of the roll used is preferably set to be 1500 mm or more. The roll length of the roll used is preferably set to be 2500 mm or less.

[0344] In addition, the tension is preferably 2.2 kgf / mm 2 More preferably 2.4 kgf / mm 2 In addition, the tension is preferably 15.0 kgf / mm 2 Below, more preferably 10.0kgf / mm 2The tension is more preferably 7.0 kgf / mm 2 Below, more preferably 4.0 kgf / mm 2 the following.

[0345] Number of passes in which the steel plate is brought into contact with a roll having a diameter of 500 mm or more and 1500 mm or less for 1 / 4 of the roll's revolution per pass: 5 passes or more

[0346] In the present invention, by making the steel sheet contact the roll with a diameter of 500 mm or more and 1500 mm or less for 1 / 4 of the roll per pass, most of the austenite is transformed into martensite due to the processing (stress, strain) induced phase transformation, and then tempered in the reheating process, so that the area ratio of fresh martensite in the final structure can be reduced, and an appropriate amount of tempered martensite can be ensured. In addition, the amount of austenite just after the second cooling process can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, the desired λ, R / t, ST and SFmax can be obtained.

[0347] The number of passes is preferably 6 or more, more preferably 7 or more.

[0348] The upper limit is not particularly limited, but the number of passes is preferably 10 passes or less, more preferably 9 passes or less.

[0349] Cooling stop temperature: below 250℃

[0350] There is no particular restriction on the cooling conditions of the second cooling process, as long as conventional methods are followed. As cooling methods, for example, gas jet cooling, spray cooling, roll cooling, water cooling and air cooling can be applied. By setting the cooling stop temperature (second cooling stop temperature) to below 250°C, an appropriate amount of austenite is transformed into martensite, and then tempered in the reheating process, so that the area ratio of fresh martensite in the final structure can be reduced, and an appropriate amount of tempered martensite can be ensured. In addition, the amount of austenite just after the second cooling process can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, the desired λ, R / t, ST and SFmax can be obtained. It should be noted that from the viewpoint of preventing surface oxidation, it is preferably cooled to below 200°C. The lower limit is not particularly limited, but is preferably set to room temperature (above -5°C and below 55°C). The average cooling rate is preferably set to 1°C / second or more, for example. In addition, the average cooling rate is preferably set to 50°C / second or less. Here, the average cooling rate (° C. / s) can be calculated by (cooling start temperature (° C.)−cooling stop temperature (° C.)) / cooling time (s).

[0351] (Reheating process)

[0352] After the second cooling step, as a reheating step, the steel sheet is reheated to a temperature range of not less than the cooling stop temperature (second cooling stop temperature) and not more than 440° C. and maintained for 20 seconds or more.

[0353] Reheating temperature: a temperature range of above the cooling stop temperature (second cooling stop temperature) and below 440°C

[0354] Reheating holding time: more than 20 seconds

[0355] In the present invention, by reheating to a cooling stop temperature (second cooling stop temperature) or higher and holding for more than 20 seconds, the diffusible hydrogen in the steel is released. In addition, the area ratio of fresh martensite in the final structure can be reduced, and an appropriate amount of tempered martensite can be ensured. In addition, the amount of austenite just after the second cooling process can be reduced, and the volume ratio of retained austenite in the final structure can be reduced. As a result, the desired λ, R / t, ST and SFmax can be obtained.

[0356] On the other hand, when the reheating temperature is higher than 440°C, when the galvanizing treatment is performed, part of the galvanizing melts and adheres to the roller, and a uniformly galvanized hot-dip galvanized steel sheet cannot be obtained. In addition, when the reheating holding time is less than 20 seconds, the diffusible hydrogen in the steel is not released in the desired amount.

[0357] Therefore, in the present invention, the temperature is reheated to a temperature range of not less than the second cooling stop temperature and not more than 440° C. and maintained for 20 seconds or more.

[0358] The reheating temperature is preferably 40°C or higher, more preferably 160°C or higher.

[0359] The reheating temperature is preferably 420°C or lower, more preferably 320°C or lower.

[0360] The reheating holding time is preferably 25 seconds or longer, more preferably 30 seconds or longer.

[0361] The reheating holding time is preferably 300 seconds or less, more preferably 200 seconds or less.

[0362] In addition, the steel plate obtained as above may be further subjected to temper rolling. When the reduction rate of temper rolling is greater than 2.00%, the yield stress may increase and the dimensional accuracy when the steel plate is formed into a component may decrease. Therefore, the reduction rate of temper rolling is preferably less than 2.00%. It should be noted that there is no particular restriction on the lower limit of the reduction rate of temper rolling, but from the perspective of productivity, it is preferably greater than 0.05%. In addition, temper rolling may be performed on a device that is continuous with the annealing device used to perform the above-mentioned processes (online), or on a device that is discontinuous with the annealing device used to perform the processes (offline). In addition, the number of temper rolling passes may be 1 time or more than 2 times. It should be noted that as long as the same elongation as temper rolling can be imparted, rolling using a leveler or the like may also be performed.

[0363] The conditions of other manufacturing methods are not particularly limited, but from the viewpoint of productivity, the above-mentioned series of treatments such as annealing, hot-dip galvanizing, and alloying treatment of the galvanized layer are preferably performed in a CGL (Continuous Galvanizing Line) which is a hot-dip galvanizing line. After hot-dip galvanizing, wiping may be performed to adjust the unit weight of the coating. It should be noted that the conditions such as plating other than the above-mentioned conditions may be in accordance with the conventional method of hot-dip galvanizing.

[0364] [3.Component]

[0365] Next, components according to one embodiment of the present invention will be described.

[0366] A component according to one embodiment of the present invention is a component formed using the above-mentioned steel plate (as a raw material). For example, the component is manufactured by subjecting the steel plate as a raw material to at least one of forming processing and joining processing.

[0367] Here, the steel sheet has TS: 780 MPa or more and has high YS and YR, excellent stamping formability (ductility, hole expansion and bendability) and fracture resistance during collision (bending fracture characteristics and axial crushing characteristics). Therefore, the component according to one embodiment of the present invention has high strength and excellent impact resistance. Therefore, the component according to one embodiment of the present invention is particularly suitable for use in impact energy absorbing components used in the automotive field.

[0368] [4. Method for manufacturing component]

[0369] Next, a method for manufacturing a member according to one embodiment of the present invention will be described.

[0370] A method for manufacturing a component according to an embodiment of the present invention includes the step of performing at least one of forming and joining on the steel plate (for example, the steel plate manufactured by the method for manufacturing a steel plate) to manufacture the component.

[0371] Here, there is no particular limitation on the forming method, and general processing methods such as stamping can be used. In addition, there is no particular limitation on the joining method, and general welding such as spot welding, laser welding, arc welding, riveting, and caulking can be used. It should be noted that there is no particular limitation on the forming conditions and joining conditions, and conventional methods can be used.

[0372] Example

[0373] A steel material having the component composition shown in Table 1 (the balance is Fe and inevitable impurities) was melted in a converter and formed into a steel slab by a continuous casting method. In Table 1, - indicates the content of the inevitable impurity level.

[0374] The obtained steel slabs were heated to 1200°C, and after heating, rough rolling and hot rolling were performed on the steel slabs to produce hot-rolled steel sheets. Next, the obtained hot-rolled steel sheets No. 1 to No. 56, No. 60 to No. 83, No. 92 to No. 106, No. 112 to No. 117 were pickled and cold-rolled to produce cold-rolled steel sheets having the plate thicknesses shown in Tables 3, 5, and 7. In addition, the obtained hot-rolled steel sheets No. 57 to No. 59, No. 84 to No. 91, No. 107 to No. 111 were pickled to produce hot-rolled steel sheets (white skin) having the plate thicknesses shown in Tables 3, 5, and 7.

[0375] Next, the obtained cold-rolled steel sheet or hot-rolled steel sheet (white skin) is subjected to a heating process, an annealing process, a first cooling process, a galvanizing process, a second cooling process and a reheating process under the conditions shown in Table 2 to obtain a steel sheet (galvanized steel sheet).

[0376] In addition, the heating process, the first plating process (metal plating process), the annealing process, the first cooling process, the second plating process (galvanizing process), the second cooling process and the reheating process are carried out under the conditions shown in Table 4 to obtain a steel plate (galvanized steel plate).

[0377] Furthermore, the treatments in the heating step, the first plating step (metal plating step), the annealing step, the first cooling step, the second cooling step, and the reheating step were performed under the conditions shown in Table 6 to obtain steel sheets.

[0378] Here, hot-dip galvanizing or alloyed galvanizing is performed in the galvanizing process shown in Table 2 and Table 4 to obtain a hot-dip galvanized steel sheet (hereinafter also referred to as GI) or an alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA). It should be noted that in Table 2 and Table 4, the types of plating processes are also expressed as "GI" and "GA". In Table 2 and Table 4, in the case of GI steel sheet, since no alloying treatment is performed, the alloying temperature is expressed as -. In addition, in Table 6, when no galvanizing treatment is performed, it is expressed as CR (cold-rolled steel sheet (unplated)) or HR (hot-rolled steel sheet (unplated)).

[0379] The galvanizing bath temperature was set to 470° C. in the case of producing either GI or GA.

[0380] Regarding the zinc coating adhesion, when manufacturing GI, it is set to 45 to 72 g / m per side. 2 When manufacturing GA, it is set to 45g / m per side. 2 .

[0381] It should be noted that the composition of the zinc coating of the hot-dip galvanized steel sheet finally obtained is that GI contains Fe: 0.1-1.0 mass%, Al: 0.2-0.33 mass%, and the balance is Zn and inevitable impurities. In addition, GA contains Fe: 8.0-12.0 mass%, Al: 0.1-0.23 mass%, and the balance is Zn and inevitable impurities.

[0382] In addition, the zinc plating layer is formed on both surfaces of the base steel sheet.

[0383] Using the obtained steel plate, the steel structure of the base steel plate was identified according to the above-mentioned points. The measurement results are shown in Tables 3, 5, and 7. In Tables 3, 5, and 7, F is ferrite, M is martensite, RA is retained austenite, M' and RA' are isolated island-shaped fresh martensite and isolated island-shaped retained austenite, B and BT are bainite and tempered bainite, TM is tempered martensite, P is pearlite, θ is carbide, and F' is unrecrystallized ferrite.

[0384] The method for measuring the surface soft layer is as follows. The thickness section (L section) of the steel plate parallel to the rolling direction is smoothed by wet grinding, and then based on JIS Z 2244-1 (2020), a Vickers hardness tester is used to measure at a load of 10 gf from a position 1 μm from the surface of the steel plate in the thickness direction to a position 100 μm in the thickness direction at 1 μm intervals. Then, the measurement is performed at 20 μm intervals until the center of the plate thickness. The area where the hardness is reduced to less than 85% compared to the hardness at the 1 / 4 position of the plate thickness is defined as a soft layer (surface soft layer), and the thickness in the thickness direction of the area is defined as the thickness of the soft layer.

[0385] In Tables 1 to 7, the underlined parts indicate that the contents are outside the appropriate range of the present invention.

[0386] In addition, tensile tests, hole expansion tests, V-bend tests, U-bend + close-fitting bend tests, V-bend + orthogonal VDA bend tests and axial crushing tests were carried out according to the following key points, and the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), ultimate hole expansion ratio (λ), R / t in the V-bend test, ultimate spacer thickness (ST) in the U-bend + close-fitting bend test, stroke at maximum load measured in the V-bend + orthogonal VDA bend test (SFmax) and the presence or absence of breakage (appearance cracks) in the axial crushing test were evaluated according to the following criteria.

[0387] ·TS

[0388] ○(Qualified): 780MPa or more

[0389] ×(Unqualified): less than 780MPa

[0390] ·YS

[0391] 〇(Qualified):

[0392] (A) When 780MPa≤TS<980MPa, 500MPa≤YS

[0393] (B) When 980MPa≤TS, 600MPa≤YS

[0394] ×(Unqualified):

[0395] (A) When 780MPa≤TS<980MPa, 500MPa>YS

[0396] (B) When 980MPa≤TS, 600MPa>YS

[0397] ·YR

[0398] 〇(Qualified):

[0399] (A) When 780MPa≤TS<980MPa, 0.64≤YR

[0400] (B) When 980MPa≤TS, 0.61≤YR

[0401] ×(Unqualified):

[0402] (A) When 780MPa≤TS<980MPa, 0.64>YR

[0403] (B) When 980MPa≤TS, 0.61>YR

[0404] ·El

[0405] 〇(Qualified):

[0406] (A) When 780MPa≤TS<980MPa, 19.0%≤El

[0407] (B) When 980MPa≤TS, 15.0%≤El

[0408] ×(Unqualified):

[0409] (A) When 780MPa≤TS<980MPa, 19.0%>El

[0410] (B) When 980MPa≤TS, 15.0%>El

[0411] ·λ

[0412] 0(Qualified): 30% or more

[0413] ×(Unqualified): Less than 30%

[0414] ·R / t

[0415] 〇(Qualified):

[0416] (A) When 780MPa≤TS<980MPa, 2.0≥R / t

[0417] (B) When 980MPa≤TS, 2.5≥R / t

[0418] ×(Unqualified):

[0419] (A) When 780MPa≤TS<980MPa, 2.0<R / t

[0420] (B) When 980MPa≤TS, 2.5<R / t

[0421] ·ST

[0422] 〇(Qualified):

[0423] (A) When 780MPa≤TS<980MPa, 2.5mm≥ST

[0424] (B) When 980MPa≤TS, 4.0mm≥ST

[0425] ×(Unqualified):

[0426] (A) When 780MPa≤TS<980MPa, 2.5mm<ST

[0427] (B) When 980MPa≤TS, 4.0mm<ST

[0428] SFmax

[0429] 〇(passed)

[0430] (A) When 780MPa≤TS<980MPa, 28.0mm≤SFmax

[0431] (B) When 980MPa≤TS, 26.5mm≤SFmax

[0432] ×(Unqualified):

[0433] (A) When 780MPa≤TS<980MPa, 28.0mm>SFmax

[0434] (B) When 980MPa≤TS, 26.5mm>SFmax

[0435] Whether there is any shaft crushing or fracture (appearance cracks)

[0436] ◎ (Pass): No external cracks were observed in the sample after the shaft crushing test.

[0437] ○ (Pass): No more than one external crack was observed in the sample after the shaft crushing test

[0438] × (failed): Two or more external cracks were observed in the sample after the shaft crushing test

[0439] (1) Tensile test

[0440] The tensile test was performed based on JIS Z 2241 (2011). That is, a JIS 5 test piece was cut from the obtained steel plate so that the length direction was perpendicular to the rolling direction of the base steel plate. The tensile test was performed using the cut test piece under the condition of a crosshead speed of 10 mm / min to measure TS, YS, YR and E1. The results are shown in Table 3, Table 5, and Table 7.

[0441] (2) Hole expansion test

[0442] The hole expansion test is carried out based on JIS Z 2256 (2020). That is, a test piece of 100 mm × 100 mm is cut from the obtained steel plate by shearing. For the test piece, the gap is set to 12.5% ​​and a hole with a diameter of 10 mm is punched out. Next, a die with an inner diameter of 75 mm is used to apply an anti-wrinkle force of 9 tons (88.26 kN) around the hole, and a conical punch with a vertex angle of 60° is pressed into the hole to measure the diameter of the hole of the test piece at the crack generation limit (when cracks occur). Then, the limiting hole expansion rate is calculated by the following formula: λ (%). It should be noted that λ is an indicator for evaluating stretch flangeability. The results are shown in Tables 3, 5, and 7.

[0443] λ(%)={(D f -D0) / D0}×100

[0444] Here,

[0445] D f : The diameter of the hole of the test piece when cracks occurred (mm),

[0446] D0: initial diameter of the hole of the test piece (mm).

[0447] (3) V bending test

[0448] The V (90°) bending test was performed based on JIS Z 2248 (2014).

[0449] A test piece of 100 mm×35 mm was cut out from the obtained steel plate by shearing and end grinding, wherein the 100 mm side was parallel to the width (C) direction.

[0450] Bending radius R: varies in steps of 0.5 mm

[0451] Test method: Die support, punch press

[0452] Forming load: 10 tons

[0453] Test speed: 30mm / min

[0454] Hold time: 5s

[0455] Bending direction: rolling right angle (C) direction

[0456] The evaluation was performed three times, and R / t was calculated by dividing the minimum bending radius (limit bending radius) R without cracks by the plate thickness t. In addition, using a solid microscope manufactured by Leica, cracks with a length of 200 μm or more at a magnification of 25 times were judged as cracks. It should be noted that when TS is 780 MPa or more and less than 980 MPa, 2.0 ≥ R / t is judged as good, and when TS is 980 MPa or more, 2.5 ≥ R / t is judged as good.

[0457] (4) U-bend + close-fitting bend test

[0458] The U-bend + close bend test was performed as follows.

[0459] A 60 mm x 30 mm test piece was cut from the obtained steel plate by shearing and end grinding. Here, the 60 mm side is parallel to the width (C) direction. The test piece was prepared by performing U bending (primary bending) in the width (C) direction with a curvature radius / plate thickness of 4.2 and with the rolling (L) direction as the axis. In the U bending (primary bending), if Figure 2 As shown in (a), a punch B1 is pressed into a steel sheet placed on a roller A1 to obtain a test piece T1. Figure 2 As shown in (b), the test piece T1 placed on the lower die A2 is subjected to close bending (secondary bending) by being crushed by the upper die B2. Figure 2 In (a), D1 indicates the width (C) direction, and D2 indicates the rolling (L) direction. In addition, a spacer S described later was inserted between the test pieces.

[0460] The conditions for U-bending in the U-bending + close-fitting bending test are as follows.

[0461] Test method: Roller support, punch press

[0462] Punch tip R: 5.0mm

[0463] Gap between roller and punch: Plate thickness + 0.1mm

[0464] Stroke speed: 10mm / min

[0465] Bending direction: rolling right angle (C) direction

[0466] The conditions for close bending in the U-bending + close bending test are as follows.

[0467] Spacer thickness: varies in 0.5mm steps

[0468] Test method: Die support, punch press

[0469] Forming load: 10 tons

[0470] Test speed: 10mm / min

[0471] Hold time: 5s

[0472] Bending direction: rolling right angle (C) direction

[0473] The above-mentioned U-bend + close-fitting bend test was carried out three times, and the limit spacer thickness (ST) was taken as the one when no cracks were generated in the three times. In addition, a solid microscope manufactured by Leica was used to judge cracks with a length of more than 200 μm at a magnification of 25 times as cracks. It should be noted that ST is an indicator for evaluating the fracture resistance during collision (fracture resistance of the longitudinal wall in the axial crushing test). The results are shown in Tables 3, 5, and 7.

[0474] (5) V-bend + orthogonal VDA bending test

[0475] The V-bend + orthogonal VDA bend test was performed as follows.

[0476] A 60 mm x 65 mm test piece was cut from the obtained steel plate by shearing and end grinding. Here, the 60 mm side is parallel to the rolling (L) direction. The test piece was prepared by bending 90° (primary bending) in the rolling (L) direction with a curvature radius / plate thickness of 4.2 and with the width (C) direction as the axis. In the 90° bending (primary bending), if Figure 3 As shown in (a), a punch B3 is pressed into a steel plate placed on a die A3 having a V-shaped groove to obtain a test piece T1. Figure 3 As shown in (b), the test piece T1 placed on the support roll A4 is subjected to orthogonal bending (secondary bending) by pressing the punch B4 so that the bending direction is at a right angle to the rolling direction. Figure 3 (a) and Figure 3 In (b), D1 indicates the width (C) direction, and D2 indicates the rolling (L) direction.

[0477] The conditions of the V-bend in the V-bend + orthogonal VDA bend test are as follows.

[0478] Test method: Die support, punch press

[0479] Forming load: 10 tons

[0480] Test speed: 30mm / min

[0481] Hold time: 5s

[0482] Bending direction: rolling (L) direction

[0483] The conditions of VDA bending in the V bending + orthogonal VDA bending test are as follows.

[0484] Test method: Roller support, punch press

[0485] Roller diameter: φ30mm

[0486] Punch tip R: 0.4mm

[0487] Distance between rollers: (plate thickness × 2) + 0.5 mm

[0488] Stroke speed: 20mm / min

[0489] Test piece size: 60mm×60mm

[0490] Bending direction: rolling right angle (C) direction

[0491] In the stroke-load curve obtained when performing the above-mentioned VDA bending, the stroke at the maximum load is calculated. The average value of the stroke at the maximum load when performing the above-mentioned V bending + orthogonal VDA bending test three times is taken as SFmax (mm). It should be noted that SFmax is an index for evaluating the fracture resistance during collision (fracture resistance of the bending ridge in the axial crushing test). The results are shown in Tables 3, 5, and 7.

[0492] (6) Shaft crush test

[0493] A 160 mm x 200 mm test piece was cut from the obtained steel plate by shearing. Here, the 160 mm side was set to be parallel to the rolling (L) direction. A die with a punch shoulder radius of 5.0 mm and a die shoulder radius of 5.0 mm was used to perform forming (bending) to a depth of 40 mm to produce Figure 4 (a) and Figure 4 (b) The hat-shaped member 10 shown in FIG. 1 is a hat-shaped member 10. In addition, the steel plate used as the raw material of the hat-shaped member is cut into a size of 80 mm × 100 mm. Then, the cut steel plate 20 and the hat-shaped member 10 are spot welded to produce a hat-shaped member 10 as shown in FIG. Figure 4 (a) and Figure 4 (b) is a test member 30 shown. Figure 4 (a) is a front view of a test member 30 produced by spot welding a hat-shaped member 10 and a steel plate 20 . Figure 4 (b) is a perspective view of the test component 30. The position of the spot weld 40 is as follows: Figure 4 As shown in (b), the ends of the steel plates are arranged so that the interval between the ends and the welded portions is 10 mm and the interval between the welded portions is 45 mm. Figure 4 As shown in (c), the test member 30 and the bottom plate 50 are joined by TIG welding to produce a shaft crush test sample. Then, the impactor 60 is made to collide with the produced shaft crush test sample at a constant speed of 10 mm / min, and the shaft crush test sample is crushed by 70 mm. Figure 4 As shown in (c), the crushing direction D3 was set to be parallel to the longitudinal direction of the test member 30. The results are shown in Tables 3, 5, and 7.

[0494] In the U-bend + close bend test, V-bend + orthogonal VDA bend test and axial crush test of steel plates with a thickness greater than 1.2 mm, all tests were conducted using steel plates with a thickness of 1.2 mm, taking into account the influence of the plate thickness. For steel plates with a thickness greater than 1.2 mm, single-sided grinding was performed to reduce the plate thickness to 1.2 mm.

[0495] Since the bending property of the steel plate surface may be affected by grinding, the ground surface is set to the inner side (valley side) of the bend in the U-bend + close-fit bend test, and the ground surface is set to the outer side (peak side) of the bend in the V-bend test, and the ground surface is set to the inner side (valley side) of the bend in the subsequent VDA bend test. On the other hand, in the U-bend + close-fit bend test, the V-bend + orthogonal VDA bend test, and the axial crushing test of the steel plate with a thickness of less than 1.2 mm, the test is performed without grinding because the influence of the plate thickness is small.

[0496] <Nanohardness measurement>

[0497] In order to obtain excellent bendability during stamping and excellent bending fracture characteristics during collision, it is more preferred to measure the nanohardness of more than 300 points in the 50μm×50μm area of ​​the plate surface at each position of 1 / 4 position of the plate thickness direction depth of the surface soft layer from the base surface layer and 1 / 2 position of the plate thickness direction depth, and the nanohardness of the plate surface at the 1 / 4 position of the plate thickness direction depth of the surface soft layer from the base steel plate surface is 7.0GPa. The total number of measurements relative to the 1 / 4 position of the plate thickness direction depth is less than 0.10. When the ratio of nanohardness to more than 7.0GPa is less than 0.10, it means that the ratio of hard tissues (martensite, etc.), inclusions, etc. is small, so that the generation, connection and expansion of cracks in the hard tissues (martensite, etc.), inclusions, etc. during stamping and collision can be further suppressed, and excellent R / t and SFmax can be obtained.

[0498] In this embodiment, when plating is performed, after stripping the plating layer, mechanical grinding is performed to the position of 1 / 4 of the depth in the thickness direction of the surface soft layer from the surface of the base steel plate to -5 μm, diamond and alumina polishing is performed to the position of 1 / 4 of the depth in the thickness direction of the surface soft layer from the surface of the base steel plate, and then colloidal silica grinding is performed. Using Hysitron's tribo-950, a berkovich-shaped diamond indenter is used to measure the nanohardness of a total of 512 points under the conditions of load: 500 μN, measurement area: 50 μm×50 μm, and dot interval: 2 μm.

[0499] Next, mechanical grinding, polishing with diamond and alumina, and colloidal silica grinding were performed until the 1 / 2 position of the depth in the thickness direction of the surface soft layer. Using Hysitron's tribo-950, a berkovich-shaped diamond indenter was used to measure the nanohardness of a total of 512 points under the conditions of load: 500 μN, measurement area: 50 μm×50 μm, and dot interval: 2 μm.

[0500]

[0501]

[0502]

[0503]

[0504]

[0505]

[0506]

[0507]

[0508]

[0509]

[0510]

[0511]

[0512] As shown in Tables 3, 5 and 7, for the inventive examples, the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), ultimate hole expansion ratio (λ), R / t in the V-bending test, the ultimate spacer thickness (ST) in the U-bending + close-fitting bending test, and the stroke at the maximum load measured in the V-bending + orthogonal VDA bending test (SFmax) were all qualified, and there was no breakage (appearance crack) in the axial crushing test.

[0513] On the other hand, with regard to the comparative examples, at least one of the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limiting hole expansion ratio (λ), R / t in the V-bend test, limiting spacer thickness (ST) in the U-bend + close-fit bend test, the stroke at the maximum load measured in the V-bend + orthogonal VDA bend test (SFmax), and the presence or absence of fracture (appearance cracks) in the axial crush test is insufficient.

[0514] It should be noted that in Tables 5 and 7, although there are cases where the dew point is in the range of above -30°C and below -5°C, the thickness of the soft layer on the surface is below 17μm, and the fracture (appearance crack) in the shaft crush test is judged as "○", even when the thickness of the soft layer on the surface is below 17μm, in the case of having a metal plating layer, the fracture (appearance crack) in the shaft crush test is judged as "◎".

[0515] In addition, it can be seen that the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limiting hole expansion ratio (λ), R / t in the V-bending test, the limiting spacer thickness (ST) in the U-bending + close-fitting bending test, and the stroke (SFmax) at the maximum load measured in the V-bending + orthogonal VDA bending test of the components obtained by forming or joining the steel plates of the examples of the present invention all have the excellent characteristics that are characteristic of the present invention, and there is no fracture (appearance crack) in the axial crushing test, and the components have the excellent characteristics that are characteristic of the present invention.

[0516] Explanation of symbols

[0517] 10 Hat-shaped components

[0518] 20 steel plate

[0519] 30Test components

[0520] 40 spot welding

[0521] 50 base plate

[0522] 60 Impactor

[0523] A1 Die

[0524] A2 support roller

[0525] A3 die

[0526] A4 support roller

[0527] B1 Punch

[0528] B2 Punch

[0529] B3 punch

[0530] B4 punch

[0531] D1 width (C) direction

[0532] D2 rolling (L) direction

[0533] D3 crush direction

[0534] S Spacer

[0535] T1 test piece

[0536] F Ferrite

[0537] M Martensite

[0538] RA Retained austenite

[0539] M' isolated island fresh martensite

[0540] RA' isolated islands of retained austenite

[0541] B Bainite

[0542] BT tempered bainite

[0543] TM tempered martensite

[0544] Industrial Applicability

[0545] According to the present invention, it is possible to manufacture steel plates and components having a TS of 780 MPa or more, high YS and YR, excellent stamping formability (ductility, hole expansion and bendability) and fracture resistance during collision (bending fracture characteristics and axial crushing characteristics). In addition, by applying the steel plates and components obtained by the method according to the present invention to, for example, automotive structural components, it is possible to achieve improved fuel efficiency due to lightweighting of the vehicle body, and the industrial utilization value is extremely high.

Claims

1. A steel plate comprising a base steel plate, in, The base steel plate has a composition containing, in mass%, C: 0.030% to 0.250% inclusive, Si: 0.01% to 0.75% inclusive, Mn: 2.00% to less than 3.50%, P: 0.001% to 0.100% inclusive, S: 0.0200% to inclusive, Al: 0.010% to 2.000% inclusive, N: 0.0100% to inclusive, and the balance being Fe and inevitable impurities, and A steel structure having, in terms of the structure at a position 1 / 4 of the plate thickness of the base steel plate, an area ratio of ferrite of 20.0% or more and 80.0% or less, an area ratio of fresh martensite of 15.0% or less, an area ratio of retained austenite of 3.0% or less, a value obtained by dividing the total area ratio of island-shaped fresh martensite and island-shaped retained austenite in ferrite grains by the total area ratio of fresh martensite and retained austenite in the entire steel plate of 0.65 or more, an area ratio of bainite and tempered bainite of 10.0% or less, an area ratio of tempered martensite of 10.0% or more and 70.0% or less, and an average grain size of island-shaped fresh martensite and island-shaped retained austenite in ferrite grains of 2.0 μm or less, The amount of diffusible hydrogen contained in the base steel plate is 0.50 mass ppm or less, The tensile strength of the steel plate is 780 MPa or more.

2. The steel plate according to claim 1, in, The composition further contains, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less. At least one element selected from the group consisting of 0.0200% or less, Co: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, and REM: 0.0200% or less.

3. The steel plate according to claim 1 or 2, in, The steel sheet has a zinc coating as an outermost layer on one or both sides thereof.

4. The steel plate according to any one of claims 1 to 3, in, When the base steel plate has a surface layer of a region of 200 μm or less in the plate thickness direction from the surface of the base steel plate, The surface layer has a surface soft layer having a Vickers hardness of 85% or less relative to the Vickers hardness at a position of 1 / 4 of the plate thickness, When the nanohardness is measured at 300 points or more in a 50 μm×50 μm area of ​​the plate surface at each of the 1 / 4 position and the 1 / 2 position of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate, The ratio of the number of measurements of the plate surface having a nanohardness of 7.0 GPa or more at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 0.10 or less relative to the total number of measurements at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer, Furthermore, the standard deviation σ of the nanohardness of the plate surface at a position 1 / 4 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 1.8 GPa or less, Furthermore, a standard deviation σ of the nanohardness of the plate surface at a position 1 / 2 of the depth in the plate thickness direction of the surface soft layer from the surface of the base steel plate is 2.2 GPa or less.

5. The steel plate according to any one of claims 1 to 4, in, The steel sheet has a metal plating layer formed on the base steel sheet on one side or both sides thereof. 6 . A member formed using the steel sheet according to claim 1 .

7. A method for manufacturing a steel plate, wherein include: A hot rolling step, wherein a steel slab having the composition described in claim 1 or 2 is hot rolled at a finishing rolling temperature of 820° C. or higher to obtain a hot rolled steel sheet; A heating step, wherein the steel sheet after the hot rolling step is heated within a temperature range of 350° C. to 600° C. at an average heating rate of 7° C. / s or more; An annealing step, wherein the annealing is performed under the conditions of an annealing temperature of 750° C. or higher and 900° C. or lower and an annealing time of 20 seconds or longer; A first cooling step, wherein cooling is performed after the annealing step under conditions where the average cooling rate from (the annealing temperature - 30°C) to 650°C is set to 7°C / sec or more, and the average cooling rate from 650°C to 500°C is set to 14°C / sec or less; The second cooling step comprises applying 2.0 kgf / mm2 to the steel plate in a temperature range of 300°C to 450°C after the first cooling step. 2 The steel sheet is subjected to a tension of at least 500 mm and at most 1500 mm, and then the steel sheet is subjected to at least 5 passes while being brought into contact with a roll having a diameter of at least 500 mm and at most 1500 mm for 1 / 4 of the roll in each pass, and then cooled to a cooling stop temperature of at most 250° C.; and a reheating step, wherein after the second cooling step, the steel sheet is reheated to a temperature in the range of not less than the cooling stop temperature and not more than 440° C. and maintained for 20 seconds or more, Alternatively, the method further includes performing cold rolling on the steel sheet after the hot rolling step and before the temperature raising step at a reduction ratio of 20% to 80% to obtain a cold-rolled steel sheet.

8. The method for manufacturing a steel plate according to claim 7, in, The method includes a galvanizing step of performing galvanizing on the steel sheet after the first cooling step and before the second cooling step to form a zinc plated layer on the steel sheet.

9. The method for manufacturing a steel plate according to claim 7 or 8, in, The annealing in the annealing step is performed in an atmosphere with a dew point of -30°C or higher.

10. The method for producing a steel plate according to any one of claims 7 to 9, in, The method includes a metal plating step of plating one or both surfaces of the steel sheet to form a metal plating layer after the hot rolling step and before the annealing step. 11 . A method for producing a member, comprising the step of subjecting the steel sheet according to claim 1 to at least one of a forming process and a joining process to produce a member.